Transfer sheet

By using color-changing components on the transfer sheet, alignment marks can be positioned at arbitrary locations using external stimuli, solving the problems of damage and low versatility in the semiconductor chip transfer process, improving manufacturing efficiency and reducing costs.

CN119301209APending Publication Date: 2025-01-10NITTO DENKO CORP

Patent Information

Application Number
CN202380046597.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-16
Filing Date
2023-06-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In existing technologies, semiconductor chips are easily damaged during the transfer process, and the alignment marks have low universality, resulting in high manufacturing efficiency and cost.

Method used

A transfer sheet containing a color-changing component that can change color upon external stimulation is used. The color-changing component changes color upon external stimulation to achieve alignment marks, enabling alignment and positioning at any location.

Benefits of technology

It improves the versatility and manufacturing efficiency of transfer sheets, reduces costs, prevents damage to semiconductor chips, and enables efficient chip transfer and mounting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The purpose of the present invention is to provide a transfer sheet which is highly versatile and which is capable of producing an alignment mark at an arbitrary position in an arbitrary step. The transfer sheet is used for receiving an electronic component. The transfer sheet according to the present invention contains a color-changing component that can change color by an external stimulus. The transfer sheet according to the present invention preferably has an adhesive layer, and the adhesive layer contains the color-changing component.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a transfer sheet. More specifically, the present invention relates to a transfer sheet that can be suitably used for transferring electronic components such as semiconductor chips. Background Art

[0002] In the manufacturing process of semiconductor devices, semiconductor wafers are usually singulated by dicing while temporarily fixed on a dicing tape, and the singulated semiconductor chips are pushed from the dicing tape side on the back side of the wafer using a pin member, picked up using a suction clamp called a collet, and mounted on a mounting substrate such as a circuit board (for example, Patent Document 1).

[0003] However, due to the progress of micro-processing technology, semiconductor chips are becoming smaller and thinner, and sometimes semiconductor chips are damaged when picked up by collets. In addition, the miniaturization and multi-layering of semiconductor devices are also developing, requiring multiple fine semiconductor chips to be densely mounted on the mounting substrate in multiple layers, and there is also the problem of poor efficiency of mounting individually using collets.

[0004] As a means for solving the above-mentioned problem, there is adopted a method of transferring individual semiconductor chips onto a transfer sheet and mounting the transferred semiconductor chips on a mounting substrate such as a circuit board at a time (for example, Patent Document 2).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2019-9203

[0008] Patent Document 2: Japanese Patent Application Publication No. 2021-197400 Summary of the invention

[0009] Problems to be solved by the invention

[0010] On a transfer sheet used for transferring semiconductor chips, alignment marks are sometimes provided in order to position the semiconductor chips at a predetermined position. In order to accurately place the semiconductor chips on the circuit on the mounting substrate, such alignment marks need to be provided at different positions according to the mounting substrate and be produced in a customized manner, which results in low versatility and high cost.

[0011] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a transfer sheet having high versatility, in which alignment marks can be formed at any position in any process.

[0012] Means used to solve problems

[0013] The present inventors have conducted intensive studies to achieve the above object and have found that alignment marks can be formed at any position and in any process by making the transfer sheet contain a color-changing component that changes color due to an external stimulus. The present invention has been completed based on these findings.

[0014] That is, the first aspect of the present invention provides a transfer sheet for receiving an electronic component, the transfer sheet containing a color-changing component capable of changing color by external stimulation. In this specification, the transfer sheet of the first aspect of the present invention is sometimes referred to as "the transfer sheet of the present invention".

[0015] The transfer sheet of the present invention is an object that receives electronic components when mounting fine and thin electronic components such as semiconductor chips on mounting substrates such as circuit boards, instead of picking them up individually using a collet or the like. By using the transfer sheet of the present invention for mounting electronic components, a plurality of electronic components that have been singulated by cutting can be received at one time without picking them up individually, and the received electronic components can be mounted on a mounting substrate with a large area by transferring them at one time, thereby significantly improving manufacturing efficiency.

[0016] The position where the transfer sheet receives the electronic component needs to be accurately arranged at a position corresponding to the circuit on the mounting substrate. Therefore, alignment marks for aligning the electronic component are usually provided on the transfer sheet. The alignment marks need to be provided at different positions according to the mounting substrate on which the electronic component is mounted and are made in a customized manner, which results in low versatility and high cost.

[0017] The transfer sheet of the present invention contains a color-changing component that can change color by external stimulation. Regarding the configuration in which the transfer sheet of the present invention contains the color-changing component, by applying the external stimulation to the transfer sheet, the color-changing component at the portion receiving the external stimulation changes color, so that the color-changing portion can be used as an alignment mark for receiving the position of the electronic component. The alignment mark can be made at any position on the transfer sheet in any process, so it has very high versatility, can significantly improve production efficiency, and can greatly reduce costs.

[0018] In the transfer sheet of the present invention, a semiconductor chip can be preferably used as the electronic component. In addition, the major diameter of the electronic component is preferably 500 μm or less. With the advancement of micro-machining technology, the miniaturization and thinning of electronic components such as semiconductor chips are constantly developing. By using the transfer sheet of the present invention to install electronic components, it is not necessary to use a collet to pick them up separately, so damage to the electronic components can be prevented.

[0019] One embodiment of the transfer sheet of the present invention preferably has an adhesive layer. The configuration of the transfer sheet of this embodiment having an adhesive layer is appropriate in the following aspects: it can be an adhesive layer for temporarily fixing the transfer sheet to a substrate (carrier substrate) serving as a base. Alternatively, it is also appropriate in the following aspects: when the adhesive layer receives electronic components, the force applied to the electronic components can be reduced, and damage to the electronic components can be suppressed. In addition, it is also appropriate in the following aspects: when the adhesive layer receives electronic components in a manner that does not contact the electronic components, the electronic components are easily received by the adhesive layer without bouncing up, and can be received with good positional accuracy.

[0020] In the transfer sheet of the above embodiment, the adhesive layer preferably contains the color changing component. This configuration is preferred from the viewpoint of facilitating preparation of a transfer sheet containing the color changing component and facilitating adjustment of the content of the color changing component.

[0021] In the transfer sheet of the above embodiment, the adhesive constituting the adhesive layer is preferably an acrylic adhesive or a urethane adhesive. This configuration is preferably an acrylic adhesive or a urethane adhesive from the viewpoint of high transparency and good visibility of the alignment mark.

[0022] Another embodiment of the transfer sheet of the present invention preferably has a laminated structure in which the adhesive layer, substrate and other adhesive layers different from the adhesive layer are laminated in sequence. In this embodiment, the substrate functions as a support of the transfer sheet of the present invention. In addition, the other adhesive layer is suitable from the following aspects: together with the adhesive layer, a double-sided adhesive sheet can be formed, and one adhesive layer can be temporarily fixed to a carrier substrate and the other adhesive layer receives an electronic component.

[0023] Effects of the Invention

[0024] For the transfer sheet of the present invention, the color-changing component changes color by applying an external stimulus, so that an alignment mark can be made at any position of the transfer sheet in any process. Therefore, it can be applied to all processing technologies including the transfer process of electronic components, has very high versatility, can significantly improve production efficiency, and can greatly reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic cross-sectional view showing one embodiment of the transfer sheet of the present invention.

[0026] Figure 2 It is a schematic cross-sectional view showing another embodiment of the transfer sheet of the present invention.

[0027] Figure 3 To indicate the use of Figure 1FIG. 1 is a schematic cross-sectional view of one embodiment of a first step in a method for transferring an electronic component to a transfer sheet shown.

[0028] Figure 4 To indicate the use of Figure 1 Schematic cross-sectional view of one embodiment of the second step in the method for transferring an electronic component to a transfer sheet shown.

[0029] Figure 5 To indicate the use of transfer Figure 4 A schematic cross-sectional view of one embodiment of a method for mounting an electronic component using a transfer sheet for an electronic component shown. DETAILED DESCRIPTION

[0030] [Transfer sheet]

[0031] The transfer sheet of the present invention is a transfer sheet for receiving electronic components, and contains a color-changing component capable of changing color by external stimulation.

[0032] The transfer sheet of the present invention is an object that receives electronic components when mounting fine and thin electronic components such as semiconductor chips on mounting substrates such as circuit boards, instead of picking them up individually using a collet or the like. By using the transfer sheet of the present invention for mounting electronic components, a plurality of electronic components that have been singulated by cutting can be received at one time without picking them up individually, and the received electronic components can be mounted on a mounting substrate with a large area by a one-time transfer, thereby significantly improving manufacturing efficiency.

[0033] [Color-changing component capable of changing color by external stimulation]

[0034] The position where the transfer sheet receives the electronic component needs to be accurately arranged at a position corresponding to the circuit on the mounting substrate. Therefore, alignment marks for aligning the electronic component are usually provided on the transfer sheet. The alignment marks need to be provided at different positions according to the mounting substrate on which the electronic component is mounted, and are made in a customized manner, which results in low versatility and high cost.

[0035] The transfer sheet of the present invention contains a color-changing component that can change color by external stimulation (hereinafter, sometimes referred to as "the color-changing component of the present invention" in this specification). For the structure in which the transfer sheet of the present invention contains the color-changing component of the present invention, by applying the external stimulation to the transfer sheet, the color-changing component of the part receiving the external stimulation changes color, and the color-changing part can be used as an alignment mark for receiving the position of the electronic component.

[0036] Therefore, the transfer sheet of the present invention can make alignment marks at any position in any process, and can be applied to all processing technologies including the transfer process of electronic components. It has very high versatility, can significantly improve production efficiency, and can greatly reduce costs.

[0037] As the above-mentioned external stimulus, for example, active energy ray irradiation such as electron beam irradiation, ultraviolet ray irradiation, laser irradiation, heating, etc. can be listed. From the viewpoint of facilitating the provision of alignment marks at any position of the transfer sheet of the present invention, active energy ray irradiation is preferred, ultraviolet ray irradiation is more preferred, and from the viewpoint of facilitating the formation of alignment marks at specific positions, ultraviolet laser irradiation is further preferred.

[0038] The “color changeable” based on external stimulation means that the color can be changed by external stimulation, and from the viewpoint of use as an alignment mark, “coloring” that changes from colorless (transparent) to colored is preferred.

[0039] The color-changing component of the present invention is not particularly limited as long as it can change color by the external stimulus, and examples thereof include a combination of a "compound that changes color by reaction with an acid" and an "acid generator", a combination of a "compound that loses color by reaction with a base" and an "base generator", photochromic compounds, etc.

[0040] [Compounds that change color by reaction with acid]

[0041] The compound that changes color by reacting with the acid constituting the color-changing component of the present invention is preferably a compound that changes from colorless (transparent) to colored by acid, and examples thereof include: leuco pigments. Leuco pigments are organic pigments whose hue changes reversibly with oxidation-reduction. The absorption wavelength can change according to the pH. More specifically, it refers to a reduced pigment having one or more hydrogen atoms that forms a pigment and develops color by adding electrons or removing electrons. Leuco pigments are pigments that are colorless or have a lighter color in a neutral or alkaline medium, but when reacting with an acidic substance or an electron-withdrawing substance, the lactone ring becomes an open-ring state and is colored as shown in the following formula. By selecting a leuco pigment that is substantially colorless or has a lighter color before removing electrons among leuco pigments, the change in coloring can be made significant, thereby improving the visual recognition of the alignment mark.

[0042]

[0043] In the above formula, R 1 and R 2 may be the same or different and represent a hydrogen atom or a hydrocarbon group. 1 and R 2 Together with the nitrogen atom to which it is bonded, it can form a 5-membered or 6-membered nitrogen-containing heterocyclic ring. 3 , R 4 , R 5 , R 6 , R 7 , R 8 and R 9may be the same or different and represent a hydrogen atom, a halogen atom, a hydrocarbon group, or -NR 10 R 11 . R 10 and R 11 can be the same or different and represent a hydrogen atom or a hydrocarbon group. 10 and R 11 Together with the nitrogen atom to which it is bonded, it can form a 5-membered or 6-membered nitrogen-containing heterocyclic ring. 6 and R 7 , R 7 and R 8 , R 8 and R 9 They may be bonded to form an aromatic hydrocarbon ring such as a benzene ring together with the benzene ring to which they are bonded.

[0044] Examples of the hydrocarbon group include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, tert-pentyl, neopentyl, and the like. 1-6 Alkyl; cyclohexyl, etc. 3-6 Cycloalkyl; phenyl, etc. 6-10 Aryl; benzyl, etc. 7-11 Aralkyl, etc. The hydrocarbon group may have C 1-6 Alkyl, halogenated C 1-6 Alkyl, halogen atom, C 1-6 Alkoxy, C 1-6 Substituents include alkoxycarbonyl, tetrahydrofuranyl, etc. Examples of the 5-membered or 6-membered nitrogen-containing heterocyclic ring include pyrrolidine, piperidine, morpholine, and the like.

[0045] The leuco dye is colored by an acid generated by irradiating the acid generator with active energy rays or heating the acid generator.

[0046] In addition, the leuco pigment may be colored by opening the lactone ring and then reacting with a base to close the lactone ring and eliminate the color. The base may be generated by irradiating the base generator described below with active energy rays or by heating.

[0047] Examples of the leuco dye include leuco compounds such as phthalide dyes (indolinylphthalide and triphenylmethanephthalide), fluoran dyes, triarylmethane dyes, diphenylmethane dyes, phenothiazine dyes, auramine dyes, spiropyran dyes, and rhodamine dyes.

[0048] The leuco dye is particularly preferably at least one leuco dye selected from the group consisting of phthalide dyes and fluoran dyes from the viewpoint of excellent color development.

[0049] The leuco pigment may be used alone or in combination of two or more.

[0050] Specific examples of the leuco pigment include the following compounds.

[0051] 2'-anilino-6'-(N,N-dipentan-1-ylamino)-3'-methyl-3H-spiro[isobenzofuran-1,9'-xanthen]-3-one, 2-anilino-3-methyl-6-dibutylaminofluoran, 2-anilino-3-methyl-6-dipentylaminofluoran, 2-anilino-3-methyl-6-[ethyl(4-methylphenyl)amino]fluoran, 3,3-bis(p-dimethylaminophenyl)-phthalide, 3,3-bis(p-dimethylaminophenyl)-6-dimethylaminophthalide (also known as crystal violet esters), 3,3-bis(p-dimethylaminophenyl)-6-diethylaminophthalide, 3,3-bis(p-dimethylaminophenyl)-6-chlorophthalide, 3,3-bis(p-dibutylaminophenyl)phthalide, 3-cyclohexylamino-6-chlorofluoran, 3-dimethylamino-5,7-dimethylfluoran, 3-(N-methyl-N-isobutyl)-6-methyl-7-anilinofluoran, 3-(N-ethyl-N-isopentyl)-6-methyl-7-anilinofluoran, 3-diethylamino-7-chlorofluoran, 3-diethylamino-7-methyl fluoran, 3-diethylamino-7,8-benzofluoran, 3-diethylamino-6-methyl-7-chlorofluoran, 3-(N-p-tolyl-N-ethylamino)-6-methyl-7-anilinofluoran, 3-pyrrolidinyl-6-methyl-7-anilinofluoran, 2-{N-(3'-trifluoromethylphenyl)amino}-6-diethylaminofluoran, 2-{3,6-bis(diethylamino)-9-(o-chloroanilino)xanthenyl}benzoic acid lactam, 3-diethylamino-6-methyl-7-(m-trichloromethylanilino) fluoran, 3-diethylamino-7-(o-chloroanilino)fluoran, 3-dibutylamino-7-(o-chloroanilino)fluoran, 3-(N-methyl-N-pentylamino)-6-methyl-7-anilinofluoran, 3-(N-methyl-N-cyclohexylamino)-6-methyl-7-anilinofluoran, 3-diethylamino-6-methyl-7-anilinofluoran, 3-diethylamino-6-methyl-7-anilinofluoran, 3-diethylamino-6-methyl-7-(2',4'-dimethylanilino)fluoran, 3-(N,N-diethylamino)-5-methyl-7-(N,N-dibenzylamino)fluoran, benzoylleucomethylene blue, 6'-chloro-8'-methoxy-benzoindolyl-spiropyran, 6'-bromo-3'-methoxy-benzoindolyl-spiropyran, 3-(2'-hydroxy-4'-dimethylaminophenyl)-3-(2'-methoxy-5'-chlorophenyl)phthalide, 3-(2'-hydroxy-4'-dimethylaminophenyl)-3-(2'-methoxy-5'-nitrophenyl)phthalide, 3-(2'-hydroxy-4'-diethylaminophenyl)-3-(2'-methoxy-5'-methylphenyl)phthalide, 3-(2'-methoxy-4'-dimethylaminophenyl)-3-(2'-hydroxy-4'-chloro-5'-methylphenyl)phthalide, morpholinyl-7-(N-propyl-trifluoromethylanilino)fluoran, 3-pyrrolidinyl-7-trifluoromethylanilinofluoran, 3-diethylamino-5-chloro-7-(N-benzyl-trifluoromethylanilino)fluoran, 3-pyrrolidinyl-7-(di-p-chlorophenyl)methylaminofluoran, 3-diethylamino-5-chloro-7-(α-phenylethylamino)fluoran, 3-(N-ethyl-p-methylanilino)-7-(α-phenylethylamino)fluoran, 3-diethylamino-7-(o-methoxycarbonylphenylamino)fluoran, 3-diethylamino-5-methyl-7-(α-phenylethylamino)fluoran, 3-diethylamino-7-piperidinylfluoran, 2-chloro-3-(N-methyltoluido)-7- (p-butylanilino)fluoran, 3-(N-methyl-N-isopropylamino)-6-methyl-7-anilinofluoran, 3-dibutylamino-6-methyl-7-anilinofluoran, 3,6-bis(dimethylamino)fluorenespiro(9,3')-6'-dimethylaminophthalide, 3-(N-benzyl-N-cyclohexylamino)-5,6-benzo-7-α-naphthylamino-4'-bromofluoran, 3-diethylamino-6-chloro-7-anilinofluoran, 3-{N-ethyl-N-(2-ethoxypropyl)amino}-6-methyl-7-anilinofluoran, 3-{N-ethyl-N-tetrahydrofurfurylamino}-6-methyl-7-anilinofluoran, 3-diethylamino-6-methyl-7-trimethylbenzene Amino-4',5'-benzofluorane, 3-(p-dimethylaminophenyl)-3-{1,1-bis(p-dimethylaminophenyl)vinyl-2-yl}phthalide, 3-(p-dimethylaminophenyl)-3-{1,1-bis(p-dimethylaminophenyl)vinyl-2-yl}-6-dimethylaminophthalide, 3-(p-dimethylaminophenyl)-3-(1-p-dimethylaminophenyl-1-phenylvinyl-2-yl)phthalide, 3-(p-dimethylaminophenyl)-3-(1-p-dimethylaminophenyl-1-p-chlorophenylvinyl-2-yl)-6-dimethylaminophthalide, 3-(4'-dimethylamino-2'-methoxy)-3-(1"-p-dimethylaminophenyl-1"-p-chlorophenyl-1",3-(4'-dimethylamino-2'-benzyloxy)-3-(1'-p-dimethylaminophenyl-1'-phenyl-1',3'-butadien-4'-yl)phthalide, 3-dimethylamino-6-dimethylamino-fluorene-9-spiro-3'(6'-dimethylamino)phthalide, 6-(diethylamino)-2-[(3-trifluoromethyl)anilino]xanthene-9-spiro- 3'-phthalide, 3,3-bis{2-(p-dimethylaminophenyl)-2-(p-methoxyphenyl)vinyl}-4,5,6,7-tetrachlorophthalide, 3-bis{1,1-bis(4-pyrrolidinylphenyl)vinyl-2-yl}-5,6-dichloro-4,7-dibromophthalide, bis(p-dimethylaminophenyl)-1-naphthalenesulfonylmethane, bis(p-dimethylaminophenyl)-1-tolylsulfonylmethane.

[0052] The compound that changes color by reaction with an acid may be used alone or in combination of two or more.

[0053] The content of the compound that changes color by reaction with an acid is preferably 0.01 to 30 parts by weight, more preferably 0.1 to 30 parts by weight, further preferably 0.1 to 20 parts by weight, and further preferably 1 to 10 parts by weight relative to 100 parts by weight of the transfer sheet. The content of the compound that changes color by reaction with an acid is within the above range, thereby enabling the alignment mark to be effectively formed by the color change caused by the compound that changes color by reaction with an acid.

[0054] [Acid generator]

[0055] The acid generator constituting the color-changing component of the present invention is a compound that generates an acid (cation) by being applied with the external stimulus. The generated acid causes the compound that changes color by reacting with the acid to change color. When the external stimulus is irradiation with active energy rays, a photoacid generator is used, and when the external stimulus is heating, a thermal acid generator is used. From the viewpoint of easily setting an alignment mark at an arbitrary position of the transfer sheet of the present invention by irradiation with active energy rays, a photoacid generator is preferred.

[0056] The photoacid generator refers to a compound that can generate an acid (cation) by irradiating active energy rays such as α-rays, β-rays, γ-rays, electron rays, neutron rays, and X-rays, not limited to ultraviolet rays, visible rays, and infrared rays. By using the photoacid generator together with a compound that changes color by reacting with the acid, the transfer sheet of the present invention can be irradiated with active energy rays to change color at any time and at any location, thereby forming an alignment mark.

[0057] The photoacid generator is not particularly limited as long as it is a compound that can generate an acid (cation) by irradiation with active energy rays, and examples thereof include sulfonium salt compounds, iodine Salt compounds, aromatic N-oxyimide sulfonates, sulfonate compounds and halomethyl substituted s-triazine derivatives, etc.

[0058] The photoacid generator is particularly preferably selected from the group consisting of sulfonium salt compounds, iodonium salt compounds, and the like, from the viewpoint of good compatibility with the binder described later constituting the transfer sheet of the present invention. The at least one compound selected from the group consisting of onium salt compounds and aromatic N-oxyimide sulfonates is particularly preferably a sulfonium salt compound.

[0059] Specific examples of sulfonium salt compounds include salts composed of cations such as dimethylphenacylsulfonium, dimethylbenzylsulfonium, dimethyl-4-hydroxyphenylsulfonium, dimethyl-4-hydroxynaphthylsulfonium, dimethyl-4,7-dihydroxynaphthylsulfonium, dimethyl-4,8-dihydroxynaphthylsulfonium, triphenylsulfonium, p-tolyldiphenylsulfonium, p-tert-butylphenyldiphenylsulfonium, diphenyl-4-phenylthiophenylsulfonium, and diphenyl-4-phenylthiophenylsulfonium, and anions such as chloride, bromide, p-toluenesulfonate, trifluoromethanesulfonate, tetrafluoroborate, tetrakis(pentafluorophenyl)borate, tetrakis(pentafluorophenyl)gallate, hexafluorophosphate, hexafluoroarsenate, hexafluoroantimonate, and nonafluorobutanesulfonate.

[0060] As iodine Salt compounds, for example, can be listed: diphenyl iodide , Bis(p-chlorophenyl)iodine , dimethylbenzene iodide 、Bis(p-tert-butylphenyl)iodide 4-isopropylphenyl-4-methylphenyl iodide 、Bis(m-nitrophenyl)iodide , 4-tert-butylphenyl phenyl iodide , p-methoxyphenyl phenyl iodide , bis(p-methoxyphenyl)iodide 4-Octyloxyphenylphenyl iodide , p-phenoxyphenyl phenyl iodide Salts composed of cations such as chloride, bromide, p-toluenesulfonate, trifluoromethanesulfonate, tetrafluoroborate, tetrakis(pentafluorophenyl)borate, tetrakis(pentafluorophenyl)gallate, hexafluorophosphate, hexafluoroarsenate, hexafluoroantimonate, and nonafluorobutanesulfonate.

[0061] Examples of the aromatic N-oxyimide sulfonate include N-(trifluoromethylsulfonyloxy)succinimide, N-(trifluoromethylsulfonyloxy)phthalimide, N-(trifluoromethylsulfonyloxy)diphenylmaleimide, N-(trifluoromethylsulfonyloxy)bicyclohept-5-ene-2,3-dicarboxylic imide, and N-(trifluoromethylsulfonyloxy)naphthalimide.

[0062] Examples of the sulfonate compound include benzoin toluenesulfonate, α-hydroxymethylbenzoin toluenesulfonate, o-nitrobenzyl p-toluenesulfonate, p-nitrobenzyl-9,10-diethoxyanthracene-2-sulfonate, etc. Specific examples of the halomethyl-substituted s-triazine derivative include 2,4,6-tris(trichloromethyl)-s-triazine, 2-methyl-4,6-bis(trichloromethyl)-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, and 2-methyl-4,6-bis(tribromomethyl)-s-triazine.

[0063] The thermal acid generator is a compound that generates an acid (cation) by heating. By using the thermal acid generator together with a compound that changes color by reaction with the acid, the transfer sheet of the present invention can be heated to change color or color any part at any time to form an alignment mark.

[0064] Examples of the thermal acid generator include arylsulfonium salts and aryliodonium salts. Salts, allene-ion complexes, quaternary ammonium salts, aluminum chelates, boron trifluoride amine complexes, etc. As anions, the same anions as those of the photoacid generators can be cited, and SbF6 - Such as antimony fluoride ions.

[0065] These acid generators can be used alone or in combination of two or more.

[0066] The acid generator is preferably 0.001 to 30 parts by weight, more preferably 0.01 to 25 parts by weight, further preferably 0.1 to 30 parts by weight, and further preferably 0.1 to 20 parts by weight, relative to 100 parts by weight of the transfer sheet of the present invention. When the content of the acid generator is within the above range, acid can be efficiently generated by irradiation with active energy rays or heating, and alignment marks can be effectively formed by discoloration caused by a compound that changes color by reaction with an acid.

[0067] [Alkali generating agent]

[0068] The transfer sheet of the present invention may contain an alkali generator. The alkali generator is a compound that generates a base by applying the external stimulus. When the external stimulus is irradiation with active energy rays, a photobase generator is used, and when the external stimulus is heating, a thermal base generator is used. From the viewpoint of being able to effectively make the alignment mark formed on the transfer sheet of the present invention disappear, a photobase generator is preferred.

[0069] When the transfer sheet of the present invention contains a photoacid generator, it is preferable to set the combination of the photoacid generator and the thermal base generator so that the base generator does not generate a base at the same timing as when the photoacid generator generates an acid by irradiation with active energy rays.

[0070] When the transfer sheet of the present invention contains a thermal acid generator, it is preferable to set the combination of the thermal acid generator and the photobase generator so that the base generator does not generate a base at the same timing as when the thermal acid generator generates an acid by heating.

[0071] The photobase generator refers to a compound that can generate a base (anion) by irradiating active energy rays such as α-rays, β-rays, γ-rays, electron rays, neutron rays, and X-rays, not limited to ultraviolet rays, visible rays, and infrared rays. By using the photobase generator together with a compound that changes color by reacting with the above-mentioned acid, the alignment mark can be eliminated at any timing by irradiating the transfer sheet of the present invention with active energy rays.

[0072] The photobase generator is not particularly limited as long as it is a compound that can generate a base (anion) by irradiation with active energy rays, and examples thereof include transition metal complexes, compounds having a benzylcarbamate structure, compounds having an o-substituted nitrobenzene structure, oximes, imidazole derivatives, benzoin compounds, compounds having an N-formylated aromatic amino group, compounds having an N-acylated aromatic amino group, compounds having an alkoxybenzylcarbamate group, compounds having a 1,4-dihydropyridine skeleton, oxime esters, quaternary ammonium salts, and the like.

[0073] The thermal base generator is a compound that can generate a base (anion) by heating. By using the thermal base generator together with the compound that changes color by reaction with the acid, the alignment mark can be eliminated at any timing by heating the transfer sheet of the present invention.

[0074] As the thermal base generator, there is no particular limitation as long as it is a compound that can generate a base (anion) by heating, and examples thereof include: carbamate derivatives such as 2-(4-biphenyl)-2-propylcarbamate and 1,1-dimethyl-2-cyanoethylcarbamate; urea derivatives such as urea and N,N,N'-trimethylurea; dihydropyridine derivatives such as 1,4-dihydronicotinamide; salts formed from acids and bases such as dicyandiamide, organic salts, and inorganic salts, etc.

[0075] These alkali generating agents can be used alone or in combination of two or more.

[0076] The amount of the alkali generator is preferably 0.001 to 30 parts by weight, more preferably 0.01 to 25 parts by weight, and even more preferably 0.1 to 20 parts by weight relative to 100 parts by weight of the transfer sheet of the present invention. When the content of the alkali generator is within the above range, a base can be efficiently generated by irradiation with active energy rays or heating, and the alignment mark can be decolorized.

[0077] [Combination of a compound that loses color by reaction with a base and a base generator]

[0078] The compound that loses color by reaction with a base constituting the color-changing component of the present invention is preferably a compound that changes from colored to colorless (transparent) by a base, and examples thereof include compounds that change color (color) by reaction of the above-mentioned leuco dye with an acid.

[0079] The compound that loses color by reaction with a base can also be produced by, for example, a reaction between a leuco dye and an acid generated by heating or the like of the thermal acid generator described above.

[0080] The compound that loses color by reaction with a base may be used alone or in combination of two or more. The content of the compound that loses color by reaction with a base is the same as that of the compound that changes color by reaction with an acid.

[0081] Examples of the base generator used in combination with the compound that loses color by reaction with a base include the same base generators as those described above, and the base generators can be used in the same content.

[0082] As a preferred embodiment of the combination of a compound that fades by reaction with a base and an alkali generator, for example, the entire surface of the transfer sheet is colored using a compound that fades by reaction with a base that is generated by a reaction between a leuco dye and an acid generated by heating or the like in the above-mentioned thermal acid generator, an external stimulus such as light is applied to a predetermined position and the position is decolorized using a base generated by the alkali generator, and the decolorized portion is used as an alignment mark.

[0083] [Photochromic compounds]

[0084] The photochromic compound constituting the color-changing component of the present invention is a compound whose molecular structure changes reversibly and color changes accordingly when irradiated with light of a specific wavelength. The portion that changes color when irradiated with light of a specific wavelength as an external stimulus can be used as an alignment mark.

[0085] The photochromic compound is not particularly limited and any material can be appropriately selected from conventionally known compounds. For example, one or more of spiropyran compounds, spirooxanes, fulgide compounds, naphthopyran compounds, bisimidazole compounds, etc. can be used according to the desired coloration.

[0086] The photochromic compound is preferably 0.01 to 30 parts by weight, more preferably 0.1 to 30 parts by weight, further preferably 0.1 to 20 parts by weight, and further preferably 1 to 10 parts by weight relative to 100 parts by weight of the transfer sheet. When the content of the photochromic compound is within the above range, the alignment mark can be effectively formed by the color change caused by the photochromic compound.

[0087] One embodiment of the transfer sheet of the present invention (sometimes referred to as "first embodiment" in this specification) comprises a pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer preferably contains the color-changing component of the present invention.

[0088] The configuration of the transfer sheet of the first embodiment having an adhesive layer is suitable in the following aspects: it can be an adhesive layer for temporarily fixing the transfer sheet to a substrate (carrier substrate) serving as a base. Alternatively, it is also suitable in the following aspects: when the adhesive layer receives electronic components, the force applied to the electronic components can be reduced, thereby suppressing damage to the electronic components. In addition, it is also suitable in the following aspects: when the adhesive layer receives electronic components in a manner that does not contact the electronic components, the electronic components are easily captured by the adhesive layer without bouncing up, and can be received with good positional accuracy.

[0089] In the first embodiment, the configuration in which the adhesive layer contains the color-changing component is suitable from the viewpoints of facilitating preparation of a transfer sheet containing the color-changing component of the present invention and facilitating adjustment of the content of the color-changing component of the present invention.

[0090] In addition, other embodiments of the transfer sheet of the present invention (sometimes referred to as "second embodiment" in this specification) also preferably have a laminated structure in which the adhesive layer, substrate and other adhesive layers different from the adhesive layer are laminated in sequence. In the second embodiment, the substrate functions as a support for the transfer sheet of the present invention. In addition, the other adhesive layer is suitable from the following aspects: together with the adhesive layer, a double-sided adhesive sheet can be formed, and one adhesive layer can be temporarily fixed to a carrier substrate and the other adhesive layer receives an electronic component.

[0091] In the second embodiment, the adhesive layer and the other adhesive layer may be made of the same adhesive or different adhesives.

[0092] In the second embodiment, the color-changing component of the present invention may be contained only in the aforementioned pressure-sensitive adhesive layer, or may be contained in both the aforementioned pressure-sensitive adhesive layer and the aforementioned other pressure-sensitive adhesive layer.

[0093] In the transfer sheet of the second embodiment, the adhesive layer for receiving the electronic component is referred to as a "first adhesive layer", and the adhesive layer for temporarily fixing to the carrier substrate is referred to as a "second adhesive layer".

[0094] In the second embodiment, the first adhesive layer and the second adhesive layer may be formed of the same adhesive or different adhesives.

[0095] In the second embodiment, the color-changing component of the present invention may be contained in only one of the first adhesive layer and the second adhesive layer, or may be contained in both the first adhesive layer and the second adhesive layer.

[0096] In the second embodiment, when the first adhesive layer receives the electronic component or after receiving the electronic component, it is not desirable for the transfer sheet to change color due to the active energy ray irradiation. Therefore, it is preferred that the first adhesive layer does not contain a color-changing component and the second adhesive layer contains a color-changing component.

[0097] In the first and second embodiments, the compound that changes color by reaction with an acid is preferably 0.01 to 30 parts by weight, more preferably 0.1 to 30 parts by weight, further preferably 0.1 to 20 parts by weight, and further preferably 1 to 10 parts by weight, relative to 100 parts by weight of the adhesive layer (the first adhesive layer or the second adhesive layer). The content of the compound that changes color by reaction with an acid is within the above range, thereby being able to effectively form an alignment mark by discoloration caused by the compound that changes color by reaction with an acid.

[0098] In the first and second embodiments, the acid generator is preferably 0.001 to 30 parts by weight, more preferably 0.01 to 25 parts by weight, further preferably 0.1 to 30 parts by weight, and further preferably 0.1 to 20 parts by weight, relative to 100 parts by weight of the adhesive layer (the first adhesive layer or the second adhesive layer). When the content of the acid generator is within the above range, acid can be efficiently generated by irradiation with active energy rays or heating, and alignment marks can be effectively formed by discoloration caused by a compound that changes color by reaction with an acid.

[0099] In the first and second embodiments, the amount of the base generator is preferably 0.001 to 30 parts by weight, more preferably 0.01 to 25 parts by weight, and further preferably 0.1 to 20 parts by weight, relative to 100 parts by weight of the adhesive layer (the first adhesive layer or the second adhesive layer). When the amount of the base generator is within the above range, a base can be efficiently generated by irradiation with active energy rays or heating, and the alignment mark can be decolorized.

[0100] In the first and second embodiments, the content of the compound that loses color by reaction with a base and the photochromic compound in the adhesive layer is the same as the above-mentioned compound that changes color by reaction with an acid.

[0101] Hereinafter, one embodiment of the transfer sheet of the present invention will be described with reference to the drawings, but the transfer sheet of the present invention is not limited to this embodiment. Figure 1 1 is a schematic cross-sectional view showing one embodiment (second embodiment) of the transfer sheet of the present invention, wherein 1 denotes a transfer sheet, 10 denotes a substrate, 11 denotes a first adhesive layer, and 12 denotes a second adhesive layer.

[0102] like Figure 1 As shown, the transfer sheet 1 has a laminated structure in which a first adhesive layer 11, a base material 10, and a second adhesive layer 12 are laminated in sequence, and when fine and thin electronic components such as semiconductor chips are mounted on mounting substrates such as circuit substrates, the first adhesive layer 11 receives the electronic components. By using the transfer sheet 1 for mounting electronic components, the first adhesive layer 11 can receive a plurality of electronic components singulated by dicing at one time without picking them up individually, and further, the electronic components received by the first adhesive layer 11 can be mounted on a mounting substrate with a large area by a one-time transfer, thereby significantly improving manufacturing efficiency.

[0103] In this embodiment, when the first adhesive layer 11 receives an electronic component or is subjected to processing using active energy line irradiation such as laser irradiation after receiving the electronic component, in order to suppress discoloration of the first adhesive layer 11 due to the active energy line irradiation, the first adhesive layer does not contain a discoloring component, and the second adhesive layer contains a discoloring component (not shown).

[0104] [First Adhesive Layer]

[0105] The first adhesive layer is an adhesive layer for receiving and holding electronic components, preferably including a low-adhesive adhesive layer. The first adhesive layer includes a low-adhesive adhesive layer, which can reduce the force applied to the electronic components when receiving, and can suppress the damage of the electronic components, which is suitable from this point of view. In addition, when the first adhesive layer receives the electronic components in a way that does not contact the electronic components, for example, the electronic components are peeled off from the cutting tape by pressing the electronic components with a pin component, and they are dropped onto the first adhesive layer. However, when the first adhesive layer receives the dropped electronic components, it is sometimes impossible to receive the dropped electronic components with high precision. In the case of this phenomenon, the position accuracy of the electronic products is sometimes reduced, resulting in poor contact. The above-mentioned first adhesive layer includes a low-adhesive adhesive layer. The structure is suitable from the following viewpoints: when the first adhesive layer receives the electronic components in a way that does not contact the electronic components, the electronic components are easily captured by the first adhesive layer without bouncing, and can be received with good position accuracy. In addition, it is also preferred from the following viewpoints: when the electronic components received by the transfer sheet are mounted on the mounting substrate, the electronic components can be easily peeled off from the first adhesive layer.

[0106] The first adhesive layer can be made into a low-adhesive adhesive layer by adjusting the type, composition, crosslinking degree, etc. of the adhesive, and by adding a light release agent or a plasticizer to form a WBL (weak boundary layer).

[0107] The 180° peeling strength of the first adhesive layer to the PET film at 25°C is not particularly limited, but is preferably 100 mN / 25 mm or less, more preferably 50 mN / 25 mm or less, and further preferably 10 mN / 25 mm or less, from the viewpoint of good transferability to the mounting substrate without damaging the electronic component, and being able to receive the electronic component with good positional accuracy. In addition, from the viewpoint of the adhesion of the electronic component to the first adhesive layer, the 180° peeling strength of the first adhesive layer to the glass plate at 25°C is preferably 0.1 mN / 25 mm or more, and more preferably 1 mN / 25 mm or more.

[0108] The thickness of the first adhesive layer is not particularly limited, and is preferably 1 μm or more, and more preferably 3 μm or more. When the thickness is above a certain value, the first adhesive layer can easily receive the electronic components with high precision, and thus it is preferred. In addition, the upper limit of the thickness of the first adhesive layer is not particularly limited, and is preferably 100 μm or less, and more preferably 75 μm or less. When the thickness is below a certain value, it is easy to transfer the electronic components to the mounting substrate with high precision, which is preferred.

[0109] The haze of the first adhesive layer (according to JIS K7136) is not particularly limited, preferably 10% or less, more preferably 5.0% or less. When the haze is 10% or less, excellent transparency can be obtained, for example, the visual recognition of the alignment mark formed by applying external stimulation to the transfer sheet of the second embodiment is improved, which is preferred. It should be noted that the above haze can be measured, for example, as follows: the first adhesive layer is formed on a release liner, and the release liner is peeled off and attached to a slide glass (for example, a slide glass with a total light transmittance of 91.8% and a haze of 0.4%) after standing for at least 24 hours under normal conditions (23° C., 50% RH), and the obtained sample is used as a specimen and measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").

[0110] The total light transmittance of the first adhesive layer in the visible light wavelength region (according to JIS K7361-1) is not particularly limited, preferably 85% or more, more preferably 88% or more. When the total light transmittance is 85% or more, excellent transparency can be obtained, for example, the visual recognition of the alignment mark formed by applying external stimulation to the transfer sheet of the second embodiment is improved, which is preferred. It should be noted that the above-mentioned total light transmittance can be measured, for example, as follows: the first adhesive layer is formed on a release liner, and the release liner is peeled off and attached to a slide glass (for example, a slide glass with a total light transmittance of 91.8% and a haze of 0.4%) after standing for at least 24 hours under normal conditions (23° C., 50% RH), and the obtained sample is used as a sample and measured using a haze meter (Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").

[0111] The adhesive constituting the first adhesive layer is not particularly limited, and examples thereof include polysiloxane adhesives, urethane adhesives, acrylic adhesives, rubber adhesives, polyester adhesives, polyamide adhesives, epoxy adhesives, vinyl alkyl ether adhesives, fluorine-containing adhesives, etc. Among them, from the viewpoint of being able to receive electronic components with good positional accuracy without damaging them and having good transferability to the mounting substrate, and from the viewpoint of high transparency and good visual recognition of alignment marks, polysiloxane adhesives, urethane adhesives, and acrylic adhesives that are easily controlled to have low adhesion, low viscosity, and transparency are preferred, polysiloxane adhesives and urethane adhesives are more preferred, and polysiloxane adhesives and urethane adhesives are still more preferred.

[0112] [Polysilicone adhesive]

[0113] There are no particular restrictions on the polysiloxane adhesive, and known or commonly used polysiloxane adhesives can be used, for example, addition-type polysiloxane adhesives, peroxide-curable polysiloxane adhesives, condensation-type polysiloxane adhesives, etc. The polysiloxane adhesive can be either a one-component type or a two-component type. The polysiloxane adhesive can be used alone or in combination of two or more.

[0114] The above-mentioned addition type polysiloxane adhesive is generally an adhesive that generates a polysiloxane polymer by using a platinum compound catalyst such as chloroplatinic acid to make an organopolysiloxane having an alkenyl group such as vinyl on the silicon atom and an organopolysiloxane having a hydrosilyl group for addition reaction (hydrosilylation reaction). Peroxide curing type polysiloxane adhesive is generally an adhesive that generates a polysiloxane polymer by curing (crosslinking) an organopolysiloxane with a peroxide. In addition, condensation type polysiloxane adhesive is generally an adhesive that generates a polysiloxane polymer by dehydration or dealcoholization reaction between polyorganosiloxanes having a hydrolyzable silyl group such as a silanol group or an alkoxysilyl group at the end.

[0115] As the silicone-based pressure-sensitive adhesive, from the viewpoint of being easily controlled to have low adhesiveness and low viscosity, for example, a silicone-based pressure-sensitive adhesive composition containing a silicone rubber and a silicone resin can be cited.

[0116] As the above-mentioned polysiloxane rubber, there is no particular limitation as long as it is a polysiloxane-based rubber component, and for example, an organopolysiloxane having dimethylsiloxane, methylphenylsiloxane, etc. as main constituent units can be used. In addition, depending on the type of reaction, a polysiloxane rubber having an alkenyl group bonded to a silicon atom (an organopolysiloxane containing an alkenyl group; in the case of an addition reaction type), a polysiloxane rubber having at least a methyl group (in the case of a peroxide curing type), a polysiloxane rubber having a silanol group or a hydrolyzable alkoxysilyl group at the end (in the case of a condensation type), etc. can be used. In addition, the weight average molecular weight of the organopolysiloxane in the organopolysiloxane rubber is usually 150,000 or more, preferably 280,000 to 1,000,000, and particularly preferably 500,000 to 900,000.

[0117] The polysiloxane resin is not particularly limited as long as it is a polysiloxane resin used in a polysiloxane adhesive, and examples thereof include a polysiloxane resin containing an organic polysiloxane having a constituent unit selected from the group consisting of "R3Si 1 / 2 "M unit, Q unit containing the constituent unit "SiO2", and the constituent unit "RSiO 3 / 2" and a (co)polymer containing at least one of the T units of the constituent unit "R2SiO". It should be noted that R in the above structural unit represents a hydrocarbon group or a hydroxyl group. Examples of the above hydrocarbon group include: aliphatic hydrocarbon groups (alkyl groups such as methyl and ethyl), alicyclic hydrocarbon groups (cycloalkyl groups such as cyclohexyl), aromatic hydrocarbon groups (aryl groups such as phenyl and naphthyl). As the ratio (ratio) of the M unit to at least one unit selected from the Q unit, T unit and D unit, for example, the former / the latter (molar ratio) is preferably about 0.3 / 1 to about 1.5 / 1 (preferably about 0.5 / 1 to about 1.3 / 1). In such an organopolysiloxane in a polysiloxane resin, various functional groups such as a vinyl group can be introduced as needed. It should be noted that the introduced functional group can be a functional group that can undergo a crosslinking reaction. As the polysiloxane resin, an MQ resin containing an M unit and a Q unit is preferred. The weight average molecular weight of the organopolysiloxane in the polysiloxane resin is generally greater than 1000, preferably 1000 to 20000, and particularly preferably 1500 to 10000.

[0118] There is no particular limitation on the mixing ratio of the silicone rubber to the silicone resin. From the viewpoint of easy control to have low adhesiveness and low viscosity, for example, the silicone resin is preferably 100 to 220 parts by weight (particularly 120 to 180 parts by weight) relative to 100 parts by weight of the silicone rubber.

[0119] It should be noted that in the polysiloxane adhesive composition containing polysiloxane rubber and polysiloxane resin, the polysiloxane rubber and polysiloxane resin may be in a mixed state of simple mixing, or may react with each other to form a condensation product (especially a partial condensation product), a crosslinking reaction product, an addition reaction product, etc.

[0120] In addition, in the polysiloxane adhesive composition containing polysiloxane rubber and polysiloxane resin, from the viewpoint of being easily controlled to low adhesion and low viscosity, in order to make a cross-linked structure, a cross-linking agent is usually contained. As such a cross-linking agent, there is no particular restriction, and preferably a siloxane cross-linking agent (polysiloxane cross-linking agent) or a peroxide cross-linking agent can be used. The cross-linking agent can be used alone or in combination of two or more.

[0121] As the above-mentioned siloxane crosslinking agent, for example, a polyorganohydrogensiloxane having two or more hydrogen atoms bonded to silicon atoms in the molecule can be preferably used. In such a polyorganohydrogensiloxane, various organic groups other than hydrogen atoms can be bonded to the silicon atoms bonded to hydrogen atoms. As the organic group, in addition to alkyl groups such as methyl and ethyl groups; aryl groups such as phenyl groups, halogenated alkyl groups, etc. can also be listed. From the viewpoint of synthesis and handling, methyl groups are preferred. In addition, the skeleton structure of the polyorganohydrogensiloxane can have any of a linear, branched, and cyclic skeleton structure, preferably a linear skeleton structure.

[0122] As the above-mentioned peroxide crosslinking agent, for example, diacyl peroxide, alkyl peroxyester, peroxydicarbonate, monoperoxycarbonate, peroxyketal, dialkyl peroxide, hydroperoxide, ketone peroxide, etc. More specifically, for example, benzoyl peroxide, tert-butyl perbenzoate, diisopropylbenzene peroxide, tert-butylisopropylbenzene peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxyhexane, 2,4-dichloro-benzoyl peroxide, di-tert-butylperoxy-diisopropylbenzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di-tert-butylperoxyhexyne, etc. can be mentioned.

[0123] As addition type polysiloxane adhesives, for example, trade names "KR-3700", "KR-3701", "X-40-3237-1", "X-40-3240", "X-40-3291-1", and "X-40-3306" (all manufactured by Shin-Etsu Chemical Co., Ltd.) are commercially available. In addition, as peroxide curing type polysiloxane adhesives, for example, trade names "KR-100", "KR-101-10", and "KR-130" (all manufactured by Shin-Etsu Chemical Co., Ltd.) are commercially available.

[0124] The above-mentioned addition type polysiloxane adhesive composition preferably contains a curing catalyst such as a platinum catalyst. As a platinum catalyst, for example, commercially available trade names are "CAT-PL-50T" (manufactured by Shin-Etsu Chemical Co., Ltd.), "DOWSIL NC-25 Catalyst" or "DOWSIL SRX212 Catalyst" (manufactured by Dow Toray Co., Ltd.). From the perspective of the balance of the receptivity of the electronic components of the first adhesive layer, the position accuracy, the transferability to the mounting substrate, the adhesive force, etc., the content of the curing catalyst is preferably about 0.1 parts by weight to about 10 parts by weight relative to 100 parts by weight of the polysiloxane polymer (including polysiloxane rubber, polysiloxane resin, etc.) as the base polymer.

[0125] [Urethane adhesive]

[0126] The urethane adhesive is not particularly limited, and known or commonly used urethane adhesives can be used. From the viewpoint of easy control to low adhesiveness and low viscosity, a urethane adhesive composition containing a polyol, a polyfunctional isocyanate compound, and a catalyst is preferred.

[0127] As the above-mentioned polyol, any appropriate polyol may be used as long as it is a polyol having two or more hydroxyl groups. As such a polyol, for example, a polyol having two hydroxyl groups (diol), a polyol having three hydroxyl groups (triol), a polyol having four hydroxyl groups (tetraol), a polyol having five hydroxyl groups (pentaol), a polyol having six hydroxyl groups (hexaol), etc. may be cited. As the polyol, only one type may be used, or two or more types may be used.

[0128] As the above-mentioned polyol, it is preferred to include a polyol having a number average molecular weight (Mn) of 400 to 20,000. In addition, the content ratio of the polyol having a number average molecular weight (Mn) of 400 to 20,000 in the total amount of the polyol is preferably 50% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, further preferably 90% by weight to 100% by weight, particularly preferably 95% by weight to 100% by weight, and most preferably substantially 100% by weight. By adjusting the content ratio of the polyol having a number average molecular weight (Mn) of 400 to 20,000 in the polyol to be within the above range, it is possible to provide, for example, a urethane adhesive controlled to have low adhesiveness and low viscosity.

[0129] Examples of the polyol include polyester polyol, polyether polyol, polycaprolactone polyol, polycarbonate polyol, and castor oil-based polyol.

[0130] The polyester polyol can be obtained, for example, by an esterification reaction between a polyol component and an acid component.

[0131] Examples of the polyol component include ethylene glycol, diethylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 1,8-decanediol, octadecanediol, glycerol, trimethylolpropane, pentaerythritol, hexanetriol, and polypropylene glycol.

[0132] Examples of the acid component include succinic acid, methylsuccinic acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, 1,12-dodecane dicarboxylic acid, 1,14-tetradecanedioic acid, dimer acid, 2-methyl-1,4-cyclohexane dicarboxylic acid, 2-ethyl-1,4-cyclohexane dicarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, isophthalic acid, terephthalic acid, 1,4-naphthalene dicarboxylic acid, 4,4′-biphenyl dicarboxylic acid, and acid anhydrides thereof.

[0133] Examples of the polyether polyol include polyether polyols obtained by addition polymerization of alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide using water, low molecular weight polyols (propylene glycol, ethylene glycol, glycerin, trimethylolpropane, pentaerythritol, etc.), bisphenols (bisphenol A, etc.), dihydroxybenzenes (catechol, resorcinol, hydroquinone, etc.), etc. as initiators. Specifically, examples include polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.

[0134] Examples of the polycaprolactone polyol include caprolactone polyester diols obtained by ring-opening polymerization of cyclic ester monomers such as ε-caprolactone and σ-valerolactone.

[0135] Examples of the polycarbonate polyol include: polycarbonate polyols obtained by polycondensing the polyol components with phosgene; polycarbonate polyols obtained by transesterification condensation of the polyol components with carbonic acid diesters such as dimethyl carbonate, diethyl carbonate, dipropyl carbonate, diisopropyl carbonate, dibutyl carbonate, ethylbutyl carbonate, ethylene carbonate, propylene carbonate, diphenyl carbonate, and dibenzyl carbonate; copolymerized polycarbonate polyols obtained by using two or more of the polyol components; polycarbonate polyols obtained by esterification of the various polycarbonate polyols described above with carboxyl-containing compounds. polycarbonate polyols obtained by subjecting the above-mentioned various polycarbonate polyols to etherification reaction with hydroxyl-containing compounds; polycarbonate polyols obtained by subjecting the above-mentioned various polycarbonate polyols to ester exchange reaction with ester compounds; polycarbonate polyols obtained by subjecting the above-mentioned various polycarbonate polyols to ester exchange reaction with hydroxyl-containing compounds; polyester polycarbonate polyols obtained by subjecting the above-mentioned various polycarbonate polyols to condensation reaction with dicarboxylic acid compounds; copolyether polycarbonate polyols obtained by copolymerizing the above-mentioned various polycarbonate polyols with alkylene oxides, etc.

[0136] Examples of the castor oil-based polyol include castor oil-based polyols obtained by reacting castor oil fatty acids with the above-mentioned polyol components. Specifically, examples include castor oil-based polyols obtained by reacting castor oil fatty acids with polypropylene glycol.

[0137] As the above-mentioned polyol, from the viewpoints of low adhesion, low viscosity, wettability, etc. of the first adhesive layer to the electronic component, a polyol (triol) having three hydroxyl groups is preferably used as an essential component. The content of the polyol (triol) having three hydroxyl groups is preferably 50% by weight to 100% by weight, and more preferably 70% by weight to 100% by weight relative to the total amount of the components constituting the polyol.

[0138] Examples of the polyfunctional isocyanate compounds include aliphatic polyisocyanate, alicyclic polyisocyanate, and aromatic polyisocyanate compounds.

[0139] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0140] Examples of the alicyclic polyisocyanate include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.

[0141] Examples of the aromatic polyisocyanate include phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate, 4,4′-toluidine diisocyanate, 4,4′-diphenyl ether diisocyanate, 4,4′-biphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.

[0142] Among them, aliphatic polyisocyanates and their modified products are preferred. Compared with other isocyanate crosslinking agents, aliphatic polyisocyanates and their modified products have a crosslinked structure that is more flexible and can be easily controlled to have low adhesion and low viscosity. As aliphatic polyisocyanates and their modified products, hexamethylene diisocyanate and their modified products are particularly preferred.

[0143] With respect to the above-mentioned polyfunctional isocyanate compounds and the above-mentioned polyols, from the viewpoint of low adhesion, low viscosity and wettability of the first adhesive layer to electronic components, the equivalent ratio (NCO / OH) of the isocyanate group of the above-mentioned polyfunctional isocyanate compounds and the hydroxyl group of the above-mentioned polyols is preferably 1 to 5, more preferably 1.1 to 3, and further preferably 1.2 to 2.

[0144] The urethane adhesive composition preferably contains a catalyst such as an iron-containing compound and / or a tin-containing compound. Specifically, tin-containing catalysts such as dibutyltin dilaurate and dioctyltin dilaurate can be cited; tris(acetylacetonate)iron, tris(hexane-2,4-dione)iron, tris(heptane-2,4-dione)iron, tris(heptane-3,5-dione)iron, tris(5-methylhexane-2,4-dione)iron, tris(octane-2,4-dione)iron, tris(6-methylheptane-2,4-dione)iron, tris(2,6-dimethylheptane-3,5-dione)iron, tris(nonane-2,4-dione)iron, tris(nonane-4,6-dione)iron, tris(2,2,6,6-tetramethylheptane-3,5-dione)iron, tris(tridecane-6,8-dione)iron, tris(1-phenylbutane-1 ,3-diketone) iron, tris(hexafluoroacetylacetonate) iron, tris(ethyl acetoacetate) iron, tris(n-propyl acetoacetate) iron, tris(isopropyl acetoacetate) iron, tris(n-butyl acetoacetate) iron, tris(sec-butyl acetoacetate) iron, tris(tert-butyl acetoacetate) iron, tris(methyl propionoacetate) iron, tris(ethyl propionoacetate) iron, tris(n-propyl propionoacetate) iron, tris(isopropyl propionoacetate) iron, tris(n-butyl propionoacetate) iron, tris(tert-butyl propionoacetate) iron, tris(tert-butyl propionoacetate) iron, tris(benzyl acetoacetate) iron, tris(dimethyl malonate) iron, tris(diethyl malonate) iron, trimethoxy iron, triethoxy iron, triisopropoxy iron, ferric chloride and other iron-containing catalysts.

[0145] The content (usage amount) of the catalyst contained in the above-mentioned urethane adhesive composition is preferably 0.002 to 0.5 parts by weight, more preferably 0.005 to 0.3 parts by weight, and further preferably 0.01 to 0.1 parts by weight relative to 100 parts by weight of the polyol. If the content of the catalyst is within this range, the speed of the crosslinking reaction when forming the adhesive layer is fast, and the shelf life of the adhesive composition is also extended, which is a preferred embodiment.

[0146] In addition, as the urethane adhesive, a urethane adhesive composition containing a urethane prepolymer is also preferred from the viewpoint of being easy to control to have low adhesiveness and low viscosity.

[0147] The urethane adhesive composition containing the urethane prepolymer may include, for example, an adhesive composition containing a polyurethane polyol as the urethane prepolymer and a multifunctional isocyanate compound. The urethane prepolymer may be one type or two or more types. The multifunctional isocyanate compound may be one type or two or more types.

[0148] The polyurethane polyol as the urethane prepolymer is preferably obtained by reacting a polyester polyol and a polyether polyol with an organic polyisocyanate compound in the presence of a catalyst or in the absence of a catalyst.

[0149] As polyester polyol, any appropriate polyester polyol can be used. As such polyester polyol, for example, polyester polyol obtained by reacting an acid component with a diol component can be cited. As an acid component, for example, terephthalic acid, adipic acid, azelaic acid, sebacic acid, phthalic anhydride, isophthalic acid, trimellitic acid, etc. can be cited. As a diol component, for example, ethylene glycol, propylene glycol, diethylene glycol, butanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, polyoxyethylene glycol, polyoxypropylene glycol, 1,4-butanediol, neopentyl glycol, butyl ethyl pentanediol can be cited. As a polyol component, glycerol, trimethylolpropane, pentaerythritol, etc. can be cited. As polyester polyol, in addition to this, polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, poly (β-methyl-γ-valerolactone), polyvalerolactone, etc. can also be cited.

[0150] As the molecular weight of the polyester polyol, any molecular weight from low molecular weight to high molecular weight can be used. As the molecular weight of the polyester polyol, the number average molecular weight is preferably 500 to 5000. When the number average molecular weight is less than 500, the reactivity sometimes becomes high and gelation is easy. When the number average molecular weight is greater than 5000, the reactivity decreases, and the cohesive force of the polyurethane polyol itself may become smaller. The amount of the polyester polyol used is preferably 10 mol% to 90 mol% in the polyol constituting the polyurethane polyol.

[0151] As the polyether polyol, any appropriate polyether polyol can be used. Examples of such polyether polyols include polyether polyols obtained by polymerizing ethylene oxide compounds such as ethylene oxide, propylene oxide, butylene oxide, and tetrahydrofuran using low molecular weight polyols such as water, propylene glycol, ethylene glycol, glycerol, and trimethylolpropane as initiators. Specifically, examples of such polyether polyols include polyether polyols having a functional group number of 2 or more such as polypropylene glycol, polyethylene glycol, and polytetramethylene glycol.

[0152] As the molecular weight of the polyether polyol, any molecular weight from low molecular weight to high molecular weight can be used. As the molecular weight of the polyether polyol, the number average molecular weight is preferably 1000 to 5000. When the number average molecular weight is less than 1000, the reactivity sometimes becomes high and gelation is easy. When the number average molecular weight is greater than 5000, the reactivity decreases, and the cohesive force of the polyurethane polyol itself may become smaller. The amount of the polyether polyol used is preferably 20 mol% to 80 mol% in the polyol constituting the polyurethane polyol.

[0153] The polyether polyol may be partially replaced with diols such as ethylene glycol, 1,4-butanediol, neopentyl glycol, butylethylpentanediol, glycerol, trimethylolpropane, and pentaerythritol, or polyamines such as ethylenediamine, N-aminoethylethanolamine, isophoronediamine, and xylylenediamine, as needed, and used in combination.

[0154] As the polyether polyol, only bifunctional polyether polyols can be used, or part or all of polyether polyols having a number average molecular weight of 1000 to 5000 and at least 3 or more hydroxyl groups in one molecule can be used. When part or all of polyether polyols having an average molecular weight of 1000 to 5000 and at least 3 or more hydroxyl groups in one molecule are used as polyether polyols, the balance between adhesion and re-peelability can become good. In such polyether polyols, when the number average molecular weight is less than 1000, sometimes the reactivity becomes high and gelation is easy. In addition, in such polyether polyols, when the number average molecular weight is greater than 5000, the reactivity decreases, and the cohesive force of the polyurethane polyol itself may become smaller. The number average molecular weight of such polyether polyols is more preferably 2500 to 3500.

[0155] Any appropriate organic polyisocyanate compound can be used as the organic polyisocyanate compound, and examples of such organic polyisocyanate compounds include aromatic polyisocyanates, aliphatic polyisocyanates, aromatic aliphatic polyisocyanates, and alicyclic polyisocyanates.

[0156] Examples of the aromatic polyisocyanate include 1,3-phenylene diisocyanate, 4,4′-biphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4′-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4′-toluidine diisocyanate, 2,4,6-triisocyanatotoluene, benzene-1,3,5-triisocyanate, dianisidine diisocyanate, 4,4′-diphenyl ether diisocyanate, and 4,4′,4″-triphenylmethane triisocyanate.

[0157] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0158] Examples of the aromatic aliphatic polyisocyanate include ω,ω′-diisocyanate 1,3-dimethylbenzene, ω,ω′-diisocyanate 1,4-dimethylbenzene, ω,ω′-diisocyanate 1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.

[0159] Examples of the alicyclic polyisocyanate include 3-isocyanate methyl-3,5,5-trimethylcyclohexyl isocyanate, 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4′-methylenebis(cyclohexyl isocyanate), 1,4-bis(isocyanate methyl)cyclohexane, and 1,4-bis(isocyanate methyl)cyclohexane.

[0160] As the organic polyisocyanate compound, a trimethylolpropane adduct, a biuret form obtained by reaction with water, a trimer having an isocyanurate ring, and the like may be used in combination.

[0161] Any appropriate catalyst can be used as a catalyst that can be used when obtaining polyurethane polyol. Examples of such a catalyst include tertiary amine compounds and organic metal compounds.

[0162] Examples of the tertiary amine compound include triethylamine, triethylenediamine, and 1,8-diazabicyclo[5.4.0]-undecene-7 (DBU).

[0163] Examples of the organometallic compound include tin-containing compounds and non-tin-containing compounds.

[0164] Examples of the tin-containing compound include dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin dimaleate, dibutyltin dilaurate (DBTDL), dibutyltin diacetate, dibutyltin sulfide, tributyltin sulfide, tributyltin methoxy, tributyltin acetate, tributyltin ethoxy, tributyltin ethoxy, dioctyltin oxide, tributyltin chloride, tributyltin trichloroacetate, and 2-ethylhexanoic acid tin.

[0165] As non-tin-containing compounds, for example, there can be listed: titanium-containing compounds such as dibutyltitanium dichloride, tetrabutyl titanate, butoxytitanium trichloride; lead-containing compounds such as lead oleate, lead 2-ethylhexanoate, lead benzoate, lead naphthenate; iron-containing compounds such as iron 2-ethylhexanoate and iron acetylacetonate; cobalt-containing compounds such as cobalt benzoate and cobalt 2-ethylhexanoate; zinc-containing compounds such as zinc naphthenate and zinc 2-ethylhexanoate; zirconium-containing compounds such as zirconium naphthenate, etc.

[0166] When a catalyst is used when obtaining polyurethane polyol, in a system where polyester polyol and polyether polyol are present, due to their different reactivity, gelation or turbidity of the reaction solution is easily generated in a single catalyst system. Therefore, by using two catalysts when obtaining polyurethane polyol, it is easy to control the reaction rate, the selectivity of the catalyst, etc., so that these problems can be solved. As a combination of such two catalysts, for example, tertiary amine / organic metal, tin-containing type / non-tin-containing type, tin-containing type / tin-containing type can be listed, preferably tin-containing type / tin-containing type, more preferably a combination of dibutyltin dilaurate and 2-ethylhexanoic acid tin. In terms of weight ratio, its matching ratio 2-ethylhexanoic acid tin / dibutyltin dilaurate is preferably less than 1, more preferably 0.2 to 0.6. When the matching ratio is above 1, it is possible to easily gel due to the balance of catalyst activity.

[0167] When a catalyst is used to obtain the polyurethane polyol, the amount of the catalyst used is preferably 0.01% by weight to 1.0% by weight based on the total amount of the polyester polyol, the polyether polyol and the organic polyisocyanate compound.

[0168] When a catalyst is used to obtain polyurethane polyol, the reaction temperature is preferably less than 100° C., more preferably 85° C. to 95° C. If the temperature is 100° C. or higher, it may be difficult to control the reaction rate and crosslinking structure, and it may be difficult to obtain polyurethane polyol having a predetermined molecular weight.

[0169] When obtaining polyurethane polyol, a catalyst may not be used. In this case, the reaction temperature is preferably 100° C. or higher, more preferably 110° C. or higher. When obtaining polyurethane polyol without a catalyst, the reaction is preferably carried out for 3 hours or more.

[0170] As a method for obtaining polyurethane polyol, for example, there can be mentioned: 1) a method of charging all the polyester polyol, polyether polyol, catalyst, and organic polyisocyanate into a flask; 2) a method of charging the polyester polyol, polyether polyol, and catalyst into a flask and adding the organic polyisocyanate dropwise. As a method for obtaining polyurethane polyol, the method 2) is preferred in terms of controlling the reaction.

[0171] When obtaining polyurethane polyol, any appropriate solvent may be used. Examples of such solvents include methyl ethyl ketone, ethyl acetate, toluene, xylene, acetone, etc. Among these solvents, toluene is preferred.

[0172] As the polyfunctional isocyanate compound, the aforementioned compounds can be cited.

[0173] As a method for producing a polyurethane composition obtained from a composition containing a urethane prepolymer, any appropriate production method may be adopted as long as it is a method for producing a polyurethane resin composition using a so-called "urethane prepolymer" as a raw material.

[0174] [Acrylic adhesive]

[0175] The acrylic pressure-sensitive adhesive is not particularly limited, and a known or commonly used acrylic pressure-sensitive adhesive can be used. For example, from the viewpoint of easy control to low tack and low viscosity, an acrylic pressure-sensitive adhesive composition containing an acrylic polymer as a base polymer can be cited.

[0176] The acrylic polymer is a polymer containing constituent units derived from acrylic monomers (monomer components having (meth)acryloyl groups in the molecule) as constituent units of the polymer. The acrylic polymer is preferably a polymer containing the largest number of constituent units derived from (meth)acrylate in terms of mass ratio. In addition, only one type of acrylic polymer may be used, or two or more types may be used. In addition, in this specification, "(meth)acrylic acid" means "acrylic acid" and / or "methacrylic acid" (either or both of "acrylic acid" and "methacrylic acid"), and the same applies to the others.

[0177] As the above-mentioned (meth)acrylate, for example, hydrocarbon-containing (meth)acrylate can be cited. As the hydrocarbon-containing (meth)acrylate, alkyl (meth)acrylate, cycloalkyl (meth)acrylate, aryl (meth)acrylate, etc. can be cited. As the above-mentioned alkyl (meth)acrylate, for example, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, amyl, isopentyl, hexyl, heptyl, octyl, 2-ethylhexyl, isooctyl, nonyl, decyl, isodecyl, undecyl, dodecyl (lauryl), tridecyl, tetradecyl, hexadecyl, octadecyl, eicosyl, etc. can be cited. As the above-mentioned cycloalkyl (meth)acrylate, for example, cyclopentyl and cyclohexyl (meth)acrylate can be cited. As the above-mentioned aryl (meth)acrylate, for example, phenyl and benzyl (meth)acrylate can be cited.

[0178] The above-mentioned hydrocarbon group-containing (meth)acrylate may be used alone or in combination of two or more. From the viewpoint of appropriately expressing the basic characteristics such as adhesion brought by the hydrocarbon group-containing (meth)acrylate in the first adhesive layer and being easy to control to low adhesion and low viscosity, the proportion of the hydrocarbon group-containing (meth)acrylate in the total monomer components used to form the acrylic polymer is preferably 40% by mass or more, more preferably 60% by mass or more.

[0179] For the purpose of modifying cohesion, heat resistance, adhesion, viscosity, etc., the acrylic polymer may contain structural units derived from other monomer components that can be copolymerized with the hydrocarbon-containing (meth)acrylate. Examples of the other monomer components include carboxyl-containing monomers, acid anhydride monomers, hydroxyl-containing monomers, glycidyl-containing monomers, sulfonic acid-containing monomers, phosphoric acid-containing monomers, acrylamide, acrylonitrile and other functional group-containing monomers, vinyl ester monomers, etc. Examples of the carboxyl-containing monomers include acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Examples of the anhydride monomers include maleic anhydride and itaconic anhydride. Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. Examples of the glycidyl group-containing monomer include glycidyl (meth)acrylate and methyl glycidyl (meth)acrylate. Examples of the sulfonic acid group-containing monomer include styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid. Examples of the phosphoric acid group-containing monomer include 2-hydroxyethylacryloylphosphate. As the vinyl ester monomers, for example, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl pivalate, vinyl cyclohexanecarboxylate, and vinyl benzoate can be cited. Only one or more of the other monomer components can be used. From the perspective of appropriately showing the basic characteristics such as adhesion brought by the hydrocarbon-containing (meth)acrylate in the first adhesive layer and being easy to control to low adhesion and low viscosity, the total proportion of the other monomer components in all the monomer components used to form the acrylic polymer is preferably 60% by mass or less, and more preferably 40% by mass or less.

[0180] In order to form a cross-linked structure in the polymer backbone of the acrylic polymer, the acrylic polymer may contain a structural unit derived from a multifunctional monomer that can copolymerize with the monomer component that forms the acrylic polymer. Examples of the multifunctional monomer include hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy (meth)acrylate (e.g., (meth)acrylate polyglycidyl), polyester (meth)acrylate, urethane (meth)acrylate, and the like, which have (meth)acryloyl groups and other reactive functional groups in the molecule. The multifunctional monomer may be used alone or in combination of two or more. From the viewpoint of appropriately expressing the basic characteristics such as adhesion brought about by the hydrocarbon group-containing (meth)acrylate in the first adhesive layer and easily controlling the low adhesion and low viscosity, the proportion of the above-mentioned multifunctional monomer in the total monomer components used to form the acrylic polymer is preferably 40% by mass or less, and more preferably 30% by mass or less.

[0181] The acrylic polymer is obtained by polymerizing one or more monomer components including an acrylic monomer. Examples of the polymerization method include solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization.

[0182] The weight average molecular weight of the acrylic polymer is preferably 100,000 or more, more preferably 200,000 to 3,000,000. When the weight average molecular weight is 100,000 or more, there tends to be less low molecular weight substances in the pressure-sensitive adhesive layer, and contamination of electronic components and the like can be further suppressed.

[0183] The acrylic adhesive composition forming the first adhesive layer may contain a crosslinking agent. For example, the acrylic polymer may be crosslinked to further reduce the low molecular weight substances in the first adhesive layer. In addition, the weight average molecular weight of the acrylic polymer may be increased to control it to low adhesion and low viscosity. As the above-mentioned crosslinking agent, for example, polyisocyanate compounds, epoxy compounds, polyol compounds (polyphenol compounds, etc.), aziridine compounds, melamine compounds, etc. may be cited, preferably isocyanate crosslinking agents and / or epoxy crosslinking agents. When using a crosslinking agent, its usage amount is preferably about 20 weight parts or less relative to 100 weight parts of acrylic polymer, and more preferably 0.1 weight part to 15 weight parts.

[0184] As isocyanate crosslinking agents, for example, aliphatic isocyanates, alicyclic isocyanates and aromatic isocyanates can be cited. As aliphatic isocyanates, for example, trimethylene diisocyanate, butylene diisocyanate, hexamethylene diisocyanate and dimer acid diisocyanate can be cited. As alicyclic isocyanates, for example, cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate and 1,3-bis(isocyanatomethyl)cyclohexane can be cited. As aromatic isocyanates, for example, 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate and xylylene diisocyanate can be cited. Examples of the isocyanate crosslinking agent include trimethylolpropane adduct of toluene diisocyanate (trade name "CORONATEL", manufactured by Tosoh Corporation) and isocyanurate of hexamethylene diisocyanate (trade name "CORONATE HX", manufactured by Tosoh Corporation).

[0185] Examples of epoxy crosslinking agents (polyfunctional epoxy compounds) include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyols, Examples of the commercially available epoxy crosslinking agent include glycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, and bisphenol-S-diglycidyl ether. In addition, examples of the commercially available epoxy crosslinking agent include "TETRAD C" manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0186] The adhesive composition constituting the first adhesive layer preferably contains a light release agent. By containing a light release agent, a WBL (weak interface layer) is formed on the surface of the first adhesive layer, making it easy to control the adhesiveness and low viscosity.

[0187] The light release agent is not particularly limited, and a known light release agent can be used without limitation. Examples thereof include silicone release agents, fluorine-containing surfactants, and aliphatic esters. These can be used alone or in combination of two or more.

[0188] The polysiloxane release agent is not particularly limited, and examples thereof include thermosetting polysiloxane release agents, ionizing radiation curable polysiloxane release agents, etc. In addition, the polysiloxane release agent may be a solvent-free type containing no solvent, or a solvent type dissolved or dispersed in an organic solvent. It should be noted that the polysiloxane release agent may be used alone or in combination of two or more.

[0189] The heat-curable polysiloxane release agent is not particularly limited, but preferably comprises an organohydrogen polysiloxane and an organopolysiloxane having an aliphatic unsaturated group. In addition, the polysiloxane release agent is preferably a heat-addition reaction-curable polysiloxane release agent that is cured by crosslinking caused by a heat addition reaction.

[0190] The above-mentioned heat addition reaction curable polysiloxane-based release agent is not particularly limited, and the following release agents are preferably cited, which include: polysiloxane having a hydrogen atom (H) bonded to a silicon atom (Si) in the molecule (Si-H group-containing polysiloxane), and polysiloxane containing a functional group (Si-H group reactive functional group) reactive to a Si-H bond (covalent bond of Si and H) in the molecule (Si-H group reactive polysiloxane). It should be noted that the release agent is cured by cross-linking through addition reaction of Si-H groups with Si-H group reactive functional groups.

[0191] In the above-mentioned Si-H group-containing polysiloxane, Si bonded with H may be any one of Si in the main chain and Si in the side chain. The above-mentioned Si-H group-containing polysiloxane is preferably a polysiloxane containing two or more Si-H groups in the molecule. As polysiloxane containing two or more Si-H groups, dimethyl hydrogen siloxane polymers such as poly (dimethylsiloxane-methylsiloxane) are preferably cited.

[0192] In addition, as the above-mentioned Si-H group reactive polysiloxane, preferably, a polysiloxane in which a Si-H group reactive functional group or a side chain containing the functional group is bonded to Si (e.g., Si at the end of the main chain, Si inside the main chain) forming the main chain (skeleton) of the siloxane polymer is listed. Among them, a polysiloxane in which a Si-H group reactive functional group is directly bonded to Si in the main chain is preferred. In addition, as the above-mentioned Si-H group reactive polysiloxane, preferably, a polysiloxane containing two or more Si-H group reactive functional groups in the molecule is listed.

[0193] Examples of Si-H reactive functional groups in the Si-H reactive polysiloxane include alkenyl groups such as vinyl and hexenyl. In addition, examples of siloxane polymers forming the main chain portion of the Si-H reactive polysiloxane include polydialkylsiloxanes such as polydimethylsiloxane, polydiethylsiloxane, and polymethylethylsiloxane (the two alkyl groups may be the same or different); polyalkylarylsiloxanes; poly(dimethylsiloxymethylsiloxane); and polymers obtained by polymerizing a plurality of Si-containing monomers. Among them, polydimethylsiloxane is preferred as the siloxane polymer forming the main chain portion.

[0194] In particular, the thermal addition reaction curable silicone release agent is preferably a thermal addition reaction curable silicone release agent containing a polysiloxane having two or more Si—H groups in the molecule and a polysiloxane having two or more Si—H group-reactive functional groups in the molecule.

[0195] The ionizing radiation-curable silicone release agent is not particularly limited, but preferably, there is mentioned a UV-curable silicone release agent that is cured by a crosslinking reaction caused by ultraviolet (UV) irradiation.

[0196] The UV-curable silicone release agent is a release agent that is cured by a chemical reaction such as cationic polymerization, radical polymerization, radical addition polymerization, or hydrosilylation reaction caused by UV irradiation. The UV-curable silicone release agent is particularly preferably a UV-curable silicone release agent that is cured by cationic polymerization.

[0197] As a cationic polymerization type UV curable polysiloxane stripping agent, there is no particular limitation, and preferably exemplified is a stripping agent of an epoxy-containing polysiloxane, each of which is directly or via a divalent group (alkylene groups such as methylene and ethylene; alkylene groups such as ethyleneoxy and propyleneoxy, etc.) bonded to Si (e.g., Si at the end of the main chain, Si inside the main chain) and / or Si contained in the side chain forming the main chain (skeleton) of the siloxane polymer. The bonding mode of these at least two epoxy groups to Si may be the same or different. That is, preferably exemplified is a stripping agent of a polysiloxane containing two or more one or two or more epoxy-containing side chains. As side chains containing epoxy groups, glycidyl, glycidyloxy (glycidyloxy), 3,4-epoxycyclohexyl, 2,3-epoxycyclopentyl, etc. can be cited. The epoxy-containing polysiloxane may be any of a linear, branched, or a mixture thereof.

[0198] In particular, in the transfer sheet of the second embodiment, from the viewpoint of easily controlling the first adhesive layer to have low adhesiveness and low viscosity, the silicone adhesive preferably contains a heat-curable silicone release agent, and more preferably contains a thermal addition reaction-curable silicone release agent.

[0199] In the case where the first adhesive layer in the transfer sheet of the second embodiment includes a polysiloxane adhesive, the content of the polysiloxane release agent is not particularly limited, and is preferably 0.5 parts by weight or more and 100 parts by weight or less relative to 100 parts by weight of the polysiloxane polymer as the base polymer. When the above content is 0.5 parts by weight or more, it is easy to obtain the effect of easily controlling the first adhesive layer to be low adhesiveness and low viscosity, more preferably 1 part by weight or more, and further more preferably 3 parts by weight or more. In addition, when the above content is 100 parts by weight or less, it is easy to suppress the unfavorable situation that sufficient adhesiveness cannot be obtained and it is difficult to receive electronic components, more preferably 30 parts by weight or less, and further more preferably 25 parts by weight or less.

[0200] By using the above-mentioned fluorinated surfactant as a light peeling agent, it is possible to exert a light peeling effect based on the low surface free energy of the fluorinated site.

[0201] As the above-mentioned fluorinated surfactant, there is no particular limitation, for example, fluorinated oligomers, perfluorobutane sulfonates, perfluoroalkyl carboxylates, sulfonates containing hexafluoropentane trimer derivatives, carboxylates containing hexafluoropentane trimer derivatives, quaternary ammonium salts containing hexafluoropentane trimer derivatives, betaines containing hexafluoropentane trimer derivatives, polyoxyethylene ethers containing hexafluoropentane trimer derivatives, etc. can be cited, wherein fluorinated oligomers are preferred. It should be noted that the fluorinated surfactant can be used alone or in combination of two or more.

[0202] Specific examples of the fluorinated surfactants include, for example, commercially available products, such as MEGAFACE F-114 and F-410 (all manufactured by DIC Corporation), Surflon S-211, S-221, S-231, S-232, S-233, S-241, S-242, S-243, and S-420 (all manufactured by AGC SEIMI CHEMICAL Corporation), Ftergent 100, 100C, 110, 150, 150CH, 300, 310, 320, 400SW, 251, 212M, 215M, 250, 209F, 222F, 245F, 208G, 218GL, 240G, 212P, 220P, 228P, FTX-218, and DFX-18 (all manufactured by Neos Corporation). These compounds may be used alone or in combination of two or more.

[0203] The weight average molecular weight (Mw) of the above-mentioned fluorinated oligomer is preferably more than 3500, more preferably more than 5000, further preferably more than 10000, particularly preferably more than 20000. When the weight average molecular weight of the above-mentioned fluorinated oligomer is more than 3500, it is easy to control to low adhesion, low viscosity. In addition, when the weight average molecular weight is more than 20000, it is possible to suppress the foaming when the adhesive (composition) is matched, and the appearance after the adhesive is applied is excellent, so it is preferred. In addition, as the upper limit of the weight average molecular weight (Mw) of the above-mentioned fluorinated oligomer, it is preferably less than 200,000, more preferably less than 100,000. By setting the weight average molecular weight to less than 200,000, the fluorinated oligomer is easily enriched in the surface, and it is easier to play a light peeling effect, which is preferred.

[0204] Examples of the fluorinated oligomers include commercially available products such as MEGAFACE F-251, F-253, F-281, F-410, F-430, F-444, F-477, F-510, F-511, F-551, F-552, F-553, F-554, F-555, F-556, F-557, F-558, F-559, F-560, F-561, F-562, F-563, F-565, F-568, F-569, F-570, F-571, and F-572 (all manufactured by DIC Corporation), Surflon S-611, S-651, and S-386 (all manufactured by AGC SEIMICHEMICAL Corporation), and F-610. FM, 710FL, 710FM, 710FS, 730FL, 730LM (all manufactured by Neos Corporation), etc. These compounds may be used alone or in combination of two or more.

[0205] In the case where the first adhesive layer includes a fluorinated surfactant, the content of the fluorinated surfactant is not particularly limited, and is preferably 0.01 parts by weight or more and 5 parts by weight or less relative to 100 parts by weight of a polysiloxane polymer as a base polymer. When the above content is 0.01 parts by weight or more, it is easy to obtain an effect that the first adhesive layer is easily controlled to be low adhesiveness and low viscosity, more preferably 0.05 parts by weight or more, and further more preferably 0.1 parts by weight or more. In addition, when the above content is 5 parts by weight or less, it is easy to suppress the undesirable situation that sufficient adhesiveness cannot be obtained and is difficult to receive electronic components. In addition, from the viewpoint of suppressing the reduction of transparency, it is more preferably 3 parts by weight or less, and further more preferably 2 parts by weight or less.

[0206] When the adhesive composition constituting the first adhesive layer contains a fatty acid ester, low adhesion, low viscosity, and wettability of the first adhesive layer to electronic components can be expected.

[0207] As the above-mentioned fatty acid ester, for example, polyoxyethylene bisphenol A laurate, butyl stearate, 2-ethylhexyl palmitate, 2-ethylhexyl stearate, monoglyceryl behenate, 2-ethylhexanoate cetyl, isopropyl myristate, isopropyl palmitate, cholesteryl isostearate, lauryl methacrylate, coconut fatty acid methyl ester, methyl laurate, methyl oleate, methyl stearate, myristyl myristate, octyldodecyl myristate, pentaerythritol monooleate, pentaerythritol monostearate, pentaerythritol tetrapalmitate, stearyl stearate, isotridecyl stearate, glyceryl tri-2-ethylhexanoate, butyl laurate, octyl oleate, tridecyl isononanoate, etc. The fatty acid ester may be only one kind or two or more kinds.

[0208] From the viewpoint of the low adhesion, low viscosity, wettability and contamination of the first adhesive layer to electronic components, the content of the fatty acid ester contained in the above-mentioned carbamate adhesive composition is preferably 1 to 50 parts by weight, more preferably 2 to 40 parts by weight, and further preferably 3 to 30 parts by weight relative to 100 parts by weight of the polyol.

[0209] In the case where the adhesive composition constituting the first adhesive layer includes a light peeling agent, from the viewpoint of low adhesion, low viscosity, wettability, and contamination of the first adhesive layer to electronic components, its content (total amount) is preferably 0.1 parts by weight or more, more preferably 1 part by weight or more, and further preferably 3 parts by weight or more relative to 100 parts by weight of the base polymer. From the viewpoint of preventing the coloring of the first adhesive layer, it is preferably 50 parts by weight or less, more preferably 30 parts by weight or less, and further preferably 10 parts by weight or less.

[0210] The first adhesive layer may contain an ultraviolet absorber. When the first adhesive layer contains an ultraviolet absorber, discoloration caused by irradiation with active energy rays can be suppressed. Therefore, when the first adhesive layer receives an electronic component or when processing using active energy ray irradiation such as laser irradiation is performed after receiving the electronic component, discoloration of the transfer sheet can be prevented.

[0211] The ultraviolet absorber is not particularly limited, and examples thereof include triazine ultraviolet absorbers, benzotriazole ultraviolet absorbers, benzophenone ultraviolet absorbers, hydroxybenzophenone ultraviolet absorbers, salicylate ultraviolet absorbers, and cyanoacrylate ultraviolet absorbers, and these can be used alone or in combination of two or more. Among them, triazine ultraviolet absorbers and benzotriazole ultraviolet absorbers are preferred, and at least one ultraviolet absorber selected from the group consisting of triazine ultraviolet absorbers having two or less hydroxyl groups in one molecule and benzotriazole ultraviolet absorbers having one benzotriazole skeleton in one molecule has good solubility in the monomer used in the formation of the acrylic adhesive composition and has high ultraviolet absorption capacity near a wavelength of 380 nm, and is therefore preferred.

[0212] Specific examples of the triazine-based ultraviolet absorber having two or less hydroxyl groups in one molecule include 2,4-bis-[{4-(4-ethylhexyloxy)-4-hydroxy}-phenyl]-6-(4-methoxyphenyl)-1,3,5-triazine (Tinosorb S, manufactured by BASF), 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (TINUVIN460, manufactured by BASF), 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-hydroxyphenyl and [(C 10 -C 16 (Mainly C 12 -C 13 )alkoxy)methyl] ethylene oxide reaction product (TINUVIN400, manufactured by BASF), 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl]-5-[3-(dodecyloxy)-2-hydroxypropoxy]phenol), reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis-(2,4-dimethylphenyl)-1,3,5-triazine and (2-ethylhexyl)-glycidate (TINUVIN405, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol (TINUVIN1577, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]-phenol (ADK STAB LA46, manufactured by ADEKA), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (TINUVIN479, manufactured by BASF), and the like.

[0213] In addition, examples of benzotriazole ultraviolet absorbers having one benzotriazole skeleton in one molecule include 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 928, manufactured by BASF), 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (TINUVIN PS, manufactured by BASF), phenylpropionic acid, and 3-(2H-benzotriazole-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy(C 7-9 side chain and linear alkyl) ester compound (TINUVIN384-2, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN900, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN928, manufactured by BASF), methyl-3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl) propionate / polyethylene glycol 300 reaction product (TINUVIN1130, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-p-cresol (TINUVIN P, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4-6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN234, manufactured by BASF), 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol (TINUVIN326, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-amylphenol (TINUVIN328, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN VIN329, manufactured by BASF), reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl) propionate and polyethylene glycol 300 (TINUVIN213, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol (TINUVIN571, manufactured by BASF), 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole (Sumisorb250, manufactured by Sumitomo Chemical Industries, Ltd.), etc.

[0214] In addition, examples of the benzophenone-based ultraviolet absorbers (benzophenone-based compounds) and hydroxybenzophenone-based ultraviolet absorbers (hydroxybenzophenone-based compounds) include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (anhydride and trihydrate), 2-hydroxy-4-octyloxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 4-benzyloxy-2-hydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, and 2,2'-dihydroxy-4,4-dimethoxybenzophenone.

[0215] In addition, examples of the salicylate ultraviolet absorber (salicylate compound) include 2-acryloyloxyphenyl benzoate, 2-acryloyloxy-3-methylphenyl benzoate, 2-acryloyloxy-4-methylphenyl benzoate, 2-acryloyloxy-5-methylphenyl benzoate, 2-acryloyloxy-3-methoxyphenyl benzoate, 2-hydroxyphenyl benzoate, 2-hydroxy-3-methylphenyl benzoate, 2-hydroxy-4-methylphenyl benzoate, 2-hydroxy-5-methylphenyl benzoate, 2-hydroxy-3-methoxyphenyl benzoate, and 3,5-di-tert-butyl-4-hydroxybenzoic acid-2,4-di-tert-butylphenyl ester (TINUVIN120, manufactured by BASF).

[0216] Examples of the cyanoacrylate ultraviolet absorber (cyanoacrylate compound) include 2-cyanoacrylate alkyl esters, 2-cyanoacrylate cycloalkyl esters, 2-cyanoacrylate alkoxyalkyl esters, 2-cyanoacrylate alkenyl esters, and 2-cyanoacrylate alkynyl esters.

[0217] The maximum absorption wavelength of the absorption spectrum of the ultraviolet absorber preferably exists in the wavelength range of 300 nm to 400 nm, and more preferably exists in the wavelength range of 320 nm to 380 nm.

[0218] The above-mentioned ultraviolet absorber can be used alone or in combination of two or more. From the viewpoint of preventing discoloration caused by irradiation with active energy rays, the content of the ultraviolet absorber contained in the adhesive composition is preferably 0.01 to 10 parts by weight, more preferably 0.03 to 5 parts by weight, and further preferably 0.1 to 3 parts by weight, relative to 100 parts by weight of the adhesive composition.

[0219] The first adhesive layer may contain an antioxidant. When the first adhesive layer contains an antioxidant, deterioration such as discoloration during storage of the transfer sheet of the second embodiment can be suppressed.

[0220] Examples of the antioxidant include phenolic, phosphorus-containing, sulfur-containing, and amine-based antioxidants, and any one selected from these may be used. Among these, phenolic antioxidants are preferred, and hindered phenolic antioxidants are particularly preferred.

[0221] Specific examples of phenolic antioxidants include monocyclic phenol compounds such as 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-4-ethylphenol, 2,6-dicyclohexyl-4-methylphenol, 2,6-diisopropyl-4-ethylphenol, 2,6-di-tert-amyl-4-methylphenol, 2,6-di-tert-octyl-4-n-propylphenol, 2,6-dicyclohexyl-4-n-octylphenol, 2-isopropyl-4-methyl-6-tert-butylphenol, 2-tert-butyl-4-ethyl-6-tert-octylphenol, 2-isobutyl-4-ethyl-6-tert-butylphenol, 2-cyclohexyl-4-n-butyl-6-isopropylphenol, styrenated mixed cresols, DL-α-tocopherol, stearyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, etc., as bicyclic phenol compounds, there can be mentioned: 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4,4'-butylenebis(3-methyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis[6-(1-methylcyclohexyl)-p-cresol], 2,2'-ethylenebis(4,6-di-tert-butylphenol), 2,2'-butylenebis( bis(2-tert-butyl-4-methylphenol), 3,6-dioxyoctamethylenebis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2'-thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], etc. As tricyclic phenol compounds, 1,1,3-tris(2-methyl-4-hydroxybutylphenyl)butane, 1,3,5-tris(2,6-dimethyl-3-hydroxy-4-tert-butylbenzyl)propionate Examples of the present invention include tris(4-tert-butyl-2,6-dimethyl-3-hydroxybenzyl)isocyanurate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, and the like. Examples of the tetracyclic phenol compound include tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane, and examples of the phosphorus-containing phenol compound include bis(ethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate) calcium and bis(ethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate) nickel.

[0222] The above antioxidants may be used alone or in combination of two or more. From the viewpoint of suppressing deterioration such as discoloration during storage and the processability of the transfer sheet, the content of the antioxidant contained in the adhesive composition is preferably 0.01 to 10 parts by weight, more preferably 0.03 to 5 parts by weight, and further preferably 0.1 to 3 parts by weight, relative to 100 parts by weight of the adhesive composition.

[0223] The adhesive composition constituting the first adhesive layer may contain any other appropriate components within the scope of not impairing the effect of the present invention. Such other components include, for example, tackifiers, inorganic fillers, organic fillers, metal powders, pigments, foils, softeners, plasticizers, conductive agents, surface lubricants, leveling agents, heat stabilizers, inhibitors, lubricants, solvents, etc.

[0224] [Second Adhesive Layer]

[0225] The second adhesive layer is an adhesive layer for temporarily fixing to the carrier substrate, and preferably includes a peelable adhesive layer. The second adhesive layer including the peelable adhesive layer is preferred from the following aspects: the second adhesive layer can be peeled off from the carrier substrate without contamination such as adhesive residue, and the reworkability can be improved.

[0226] The second adhesive layer can be made into a releasable adhesive layer by adjusting the adhesiveness by means of the type, composition, crosslinking degree, etc. of the adhesive and reducing the adhesive force by physical stimulation such as heat, electromagnetic waves such as ultraviolet rays, etc.

[0227] The 180° peeling adhesion of the second adhesive layer to the glass plate at 25°C is not particularly limited. From the viewpoint of being able to be peeled off from the carrier substrate without contamination such as adhesive residue and improving reworkability, it is preferably 5000mN / 25mm or less, more preferably 3000mN / 25mm or less, and further preferably 1000mN / 25mm or less. In addition, from the viewpoint of adhesion between the carrier substrate and the second adhesive layer, the 180° peeling adhesion of the second adhesive layer to the glass plate at 25°C is preferably 1mN / 25mm or more, and more preferably 5mN / 25mm or more.

[0228] The 180° peel strength of the second pressure-sensitive adhesive layer at 25° C. can be measured in the same manner as that of the first pressure-sensitive adhesive layer.

[0229] The adhesive force of the second adhesive layer can be adjusted by adjusting the type, composition, crosslinking degree, etc. of the adhesive constituting the layer, or by forming a WBL (weak boundary layer) by adding a light release agent or a plasticizer.

[0230] The thickness of the second adhesive layer is not particularly limited, and is preferably 1 μm or more, and more preferably 3 μm or more. When the thickness is above a certain value, the second adhesive layer is easily and stably fixed on the carrier substrate, which is preferred. In addition, the upper limit of the thickness of the second adhesive layer is not particularly limited, and is preferably 30 μm or less, and more preferably 20 μm or less. When the thickness is below a certain value, it is easy to peel the second adhesive layer from the carrier substrate, and the reworkability is improved, which is preferred.

[0231] The haze of the second adhesive layer (according to JIS K7136) is not particularly limited, preferably 10% or less, more preferably 5% or less. When the haze is 10% or less, excellent transparency can be obtained, for example, the visual recognition of the alignment mark formed by applying external stimulation to the transfer sheet of the second embodiment is improved, which is preferred. It should be noted that the above haze can be measured, for example, as follows: the second adhesive layer is formed on a release liner, and the release liner is peeled off and attached to a slide glass (for example, a slide glass with a total light transmittance of 91.8% and a haze of 0.4%) after standing for at least 24 hours under normal conditions (23° C., 50% RH), and the obtained sample is used as a specimen and measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").

[0232] In the transfer sheet of the second embodiment, the total light transmittance of the second adhesive layer in the visible light wavelength region (according to JIS K7361-1) is not particularly limited, preferably 85% or more, more preferably 88% or more. When the total light transmittance is 85% or more, excellent transparency can be obtained, for example, the visual recognition of the alignment mark formed by applying external stimulation to the transfer sheet of the second embodiment is improved, which is preferred. It should be noted that the above-mentioned total light transmittance can be measured, for example, as follows: the second adhesive layer is formed on a release liner, and the release liner is peeled off and attached to a slide glass (for example, a slide glass with a total light transmittance of 91.8% and a haze of 0.4%) after standing for at least 24 hours under normal conditions (23°C, 50%RH), and the obtained sample is used as a sample and measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").

[0233] The adhesive constituting the second adhesive layer is not particularly limited, and examples thereof include polysiloxane adhesives, urethane adhesives, acrylic adhesives, rubber adhesives, polyester adhesives, polyamide adhesives, epoxy adhesives, vinyl alkyl ether adhesives, fluorine-containing adhesives, etc. used in the first adhesive layer. Among them, polysiloxane adhesives, urethane adhesives, and acrylic adhesives are preferred, and urethane adhesives and acrylic adhesives are more preferred, and acrylic adhesives are further preferred, from the viewpoints of being able to be peeled off from the carrier substrate without contamination such as residual adhesive and improving reworkability, and having high transparency and good visual recognition of the alignment mark.

[0234] The second adhesive layer can be an adhesive layer whose adhesive force can be intentionally reduced by external action during the use of the transfer sheet of the second embodiment (adhesion-reducing adhesive layer), or it can be an adhesive layer whose adhesive force is almost or not reduced at all by external action during the use of the transfer sheet (adhesion-non-reducing adhesive layer), and can be appropriately selected according to the method and conditions for transferring electronic components using the transfer sheet of the second embodiment.

[0235] In the case where the second adhesive layer is an adhesive layer with reduced adhesive force, the second adhesive layer can be flexibly used in the manufacturing process and use process of the transfer sheet of the second embodiment to display a state of relatively high adhesive force and a state of relatively low adhesive force. For example, in the process of using the transfer sheet of the second embodiment, in the process of receiving electronic components by the first adhesive layer, the state of the second adhesive layer displaying relatively high adhesive force can be used to suppress and prevent the transfer sheet from bulging from the carrier substrate. On the other hand, in the process of peeling the transfer sheet of the second embodiment from the carrier substrate, the reworkability can be improved by reducing the adhesive force of the second adhesive layer.

[0236] Examples of the adhesive forming the adhesive layer with reduced adhesive strength include radiation curable adhesives and heat foamable adhesives. As the adhesive forming the adhesive layer with reduced adhesive strength, one type of adhesive may be used, or two or more types of adhesives may be used.

[0237] As the radiation-curable adhesive, for example, an adhesive that is cured by irradiation with electron beams, ultraviolet rays, α rays, β rays, γ rays, or X-rays can be used, and an adhesive that is cured by irradiation with ultraviolet rays (ultraviolet-curable adhesive) can be particularly preferably used.

[0238] Examples of the radiation-curable adhesive include an addition-type radiation-curable adhesive containing a base polymer such as an acrylic polymer and a radiation-polymerizable monomer component or oligomer component having a radiation-polymerizable carbon-carbon double bond or other functional group.

[0239] As the base polymer, the same acrylic polymer as that of the first adhesive layer can be used. From the viewpoint of appropriately expressing the basic properties such as adhesion brought by the hydrocarbon-containing (meth)acrylate in the second adhesive layer and easily controlling the adhesion and peeling properties, the proportion of the hydrocarbon-containing (meth)acrylate in the total monomer components used to form the acrylic polymer is preferably 40% by mass or more, more preferably 60% by mass or more.

[0240] The acrylic polymer may contain a hydroxyl-containing monomer. When the acrylic polymer in the second adhesive layer contains a hydroxyl-containing monomer, it is easy to obtain a moderate cohesive force in the second adhesive layer. From the viewpoint of achieving moderate adhesiveness and cohesive force in the second adhesive layer, the proportion of the hydroxyl-containing monomer in the acrylic polymer is, for example, 0.1% to 30% by mass, preferably 0.5% to 20% by mass.

[0241] The acrylic polymer may contain a carboxyl group-containing monomer. When the acrylic polymer in the second adhesive layer contains a carboxyl group-containing monomer, it is easy to obtain appropriate adhesive reliability in the second adhesive layer. From the viewpoint of achieving appropriate adhesive reliability in the second adhesive layer, the proportion of the carboxyl group-containing monomer in the acrylic polymer is, for example, 0.1% to 30% by mass, preferably 0.5% to 20% by mass.

[0242] The acrylic polymer may contain a vinyl ester monomer. When the acrylic polymer in the second adhesive layer contains a vinyl ester monomer, it is easy to obtain a moderate cohesive force in the second adhesive layer. From the viewpoint of achieving a moderate cohesive force in the second adhesive layer, the proportion of the vinyl ester monomer in the acrylic polymer is, for example, 0.1% to 60% by mass, preferably 0.5% to 50% by mass.

[0243] The acrylic adhesive composition forming the second adhesive layer may contain a crosslinking agent. For example, by crosslinking the acrylic polymer, the low molecular weight substances in the second adhesive layer can be further reduced. In addition, by increasing the weight average molecular weight of the acrylic polymer, the adhesiveness and peelability can be controlled to be low. As the above-mentioned crosslinking agent, for example, polyisocyanate compounds, epoxy compounds, polyol compounds (polyphenol compounds, etc.), aziridine compounds, melamine compounds, etc. can be listed. When using a crosslinking agent preferably an isocyanate crosslinking agent and / or an epoxy crosslinking agent, the amount used is preferably about 10 parts by weight or less relative to 100 parts by weight of the acrylic polymer, and more preferably 0.1 to 10 parts by weight.

[0244] The acrylic adhesive composition forming the second adhesive layer can use a crosslinking accelerator. The type of crosslinking accelerator can be appropriately selected according to the type of crosslinking agent used. It should be noted that in this specification, the crosslinking accelerator refers to a catalyst that increases the speed of the crosslinking reaction caused by the crosslinking agent. As the crosslinking accelerator, examples include: tin (Sn) compounds such as dioctyltin dilaurate, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin diacetylacetonate, tetra-n-butyltin, and trimethyltin hydroxide; amines such as N,N,N',N'-tetramethylhexanediamine and triethylamine, imidazoles, and other N-containing compounds. Among them, Sn-containing compounds are preferred. The use of these crosslinking accelerators is particularly effective when a hydroxyl-containing monomer is used as the above-mentioned secondary monomer and an isocyanate crosslinking agent is used as the crosslinking agent. The amount of the crosslinking accelerator contained in the above-mentioned adhesive composition can be, for example, about 0.001 parts by weight to about 0.5 parts by weight (preferably about 0.001 parts by weight to about 0.1 parts by weight) relative to 100 parts by weight of the above-mentioned acrylic polymer.

[0245] Examples of the radiation-polymerizable monomer component include urethane (meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxy penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and 1,4-butanediol di(meth)acrylate. Examples of the radiation-polymerizable oligomer component include various oligomers such as urethane, polyether, polyester, polycarbonate, and polybutadiene, preferably oligomers having a molecular weight of about 100 to about 30,000. The content of the radiation-curable monomer component and oligomer component in the radiation-curable adhesive forming the second adhesive layer is, for example, about 5 parts by weight to about 500 parts by weight, and preferably about 40 parts by weight to about 150 parts by weight, relative to 100 parts by weight of the base polymer. As the additive type radiation curable adhesive, for example, an adhesive disclosed in Japanese Patent Application Laid-Open No. 60-196956 can be used.

[0246] As the radiation-curable adhesive, there can also be mentioned an intrinsic radiation-curable adhesive containing a base polymer having radiation-polymerizable carbon-carbon double bonds or other functional groups in a polymer side chain, in a polymer main chain, or at a polymer main chain terminal. When such an intrinsic radiation-curable adhesive is used, there is a tendency to suppress unexpected changes in adhesive properties over time caused by the migration of low molecular weight components in the formed second adhesive layer.

[0247] As the base polymer contained in the above-mentioned intrinsic radiation-curable adhesive, an acrylic polymer is preferred. As a method for introducing radiation-polymerizable carbon-carbon double bonds into the acrylic polymer, for example, there can be cited a method in which, after polymerizing (copolymerizing) a raw material monomer including a monomer component having a first functional group to obtain an acrylic polymer, a compound having a second functional group capable of reacting with the above-mentioned first functional group and a radiation-polymerizable carbon-carbon double bond is subjected to a condensation reaction or an addition reaction on the acrylic polymer while maintaining the radiation-polymerizable carbon-carbon double bond.

[0248] As a combination of the first functional group and the second functional group, for example, carboxyl and epoxy, epoxy and carboxyl, carboxyl and aziridine, aziridine and carboxyl, hydroxyl and isocyanate, isocyanate and hydroxyl, etc. can be cited. Among them, from the viewpoint of the ease of reaction tracking, the combination of hydroxyl and isocyanate, the combination of isocyanate and hydroxyl are preferred. Among them, from the viewpoint of the high technical difficulty of preparing a polymer having a highly reactive isocyanate group, on the other hand, the preparation of an acrylic polymer having a hydroxyl and the ease of obtaining, it is preferred that the first functional group is a hydroxyl group and the second functional group is an isocyanate. As a compound having an isocyanate group and a radiation-polymerizable carbon-carbon double bond, that is, an isocyanate compound having a radiation-polymerizable unsaturated functional group, for example, methacryloyl isocyanate, 2-methacryloyloxyethyl isocyanate, m-isopropenyl-α, α-dimethylbenzyl isocyanate, etc. can be cited. Examples of the acrylic polymer having a hydroxyl group include acrylic polymers containing a structural unit derived from the above-mentioned hydroxyl group-containing monomer, 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether and the like.

[0249] The radiation-curable adhesive preferably contains a photopolymerization initiator. Examples of the photopolymerization initiator include α-ketol compounds, acetophenone compounds, benzoin ether compounds, ketal compounds, aromatic sulfonyl chloride compounds, photoactive oxime compounds, benzophenone compounds, thioxanthone compounds, camphorquinone, halogenated ketones, acylphosphine oxides, acylphosphonates, and the like. Examples of the α-ketol compounds include 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α'-dimethylacetophenone, 2-methyl-2-hydroxypropiophenone, and 1-hydroxycyclohexylphenylketone. Examples of the acetophenone compounds include methoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone, and 2-methyl-1-[4-(methylthio)-phenyl]-2-morpholinopropane-1-one. Examples of the benzoin ether compounds include benzoin ethyl ether, benzoin isopropyl ether, and anisole methyl ether. Examples of the ketal compounds include benzil dimethyl ketal. Examples of the aromatic sulfonyl chloride compounds include 2-naphthalenesulfonyl chloride. Examples of the photoactive oxime compounds include 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime. Examples of the benzophenone compounds include benzophenone, benzoylbenzoic acid, and 3,3'-dimethyl-4-methoxybenzophenone. Examples of the thioxanthone compounds include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, and 2,4-diisopropylthioxanthone. The content of the photopolymerization initiator in the radiation-curable adhesive is, for example, 0.05 to 20 parts by weight relative to 100 parts by weight of the base polymer.

[0250] The heat-foamable adhesive is an adhesive containing a component (foaming agent, heat-expandable microspheres, etc.) that foams and expands by heating. As the foaming agent, various inorganic foaming agents and organic foaming agents can be cited. As the inorganic foaming agent, for example, ammonium carbonate, ammonium bicarbonate, sodium bicarbonate, ammonium nitrite, sodium borohydride, azides, etc. can be cited. As the above-mentioned organic foaming agent, for example, chlorofluorinated alkanes such as trichloromonofluoromethane and dichloromonofluoromethane can be listed; azo compounds such as azobisisobutyronitrile, azodicarbonamide, and barium azodicarboxylate; hydrazine compounds such as p-toluenesulfonylhydrazine, diphenylsulfone-3,3'-disulfonylhydrazine, 4,4'-oxybis(benzenesulfonylhydrazine), and allylbis(sulfonylhydrazine); semicarbazide compounds such as p-toluenesulfonylsemicarbazide and 4,4'-oxybis(benzenesulfonylsemicarbazide); triazole compounds such as 5-morpholinyl-1,2,3,4-thiazole; N-nitroso compounds such as N,N'-dinitrosopentamethylenetetramine and N,N'-dimethyl-N,N'-dinitrosoterephthalamide, etc. As the above-mentioned heat-expandable microspheres, for example, microspheres having a structure in which a substance that is easily vaporized and expanded by heating is sealed in a shell. As the material that expands by the above-mentioned heating easy gasification, for example, can enumerate isobutane, propane, pentane etc. By the material that easily gasifies and expands by heating is sealed in the shell to form the material by coagulation method, interfacial polymerization method etc., can make heat-expandable microsphere. Form material as the above-mentioned shell, can use the material that shows hot fusibility, the material that can rupture because of the effect of the thermal expansion of the sealed material. As such material, for example, can enumerate: vinylidene chloride-acrylonitrile copolymer, polyvinyl alcohol, polyvinyl butyral, polymethyl methacrylate, polyacrylonitrile, polyvinylidene chloride and polysulfone.

[0251] As the above-mentioned adhesive layer of non-reducing adhesive force, for example, a pressure-sensitive adhesive layer can be cited. It should be noted that, in the pressure-sensitive adhesive layer, about the adhesive layer of reducible adhesive force, it includes an adhesive layer of a form in which the adhesive layer formed by the above-mentioned radiation-curable adhesive is cured by radiation irradiation in advance and has a certain adhesive force. As an adhesive forming an adhesive layer of non-reducing adhesive force, one adhesive can be used, or two or more adhesives can be used. In addition, the whole of the second adhesive layer can be an adhesive layer of non-reducing adhesive force, or a part of it can be an adhesive layer of non-reducing adhesive force. For example, in the case where the second adhesive layer has a monolayer structure, the whole of the second adhesive layer can be an adhesive layer of non-reducing adhesive force, a specific part in the second adhesive layer can be an adhesive layer of non-reducing adhesive force, and other parts can be adhesive layers of reducible adhesive force. In addition, in the case where the second adhesive layer has a laminated structure, all adhesive layers in the laminated structure can be adhesive layers of non-reducing adhesive force, and a part of adhesive layers in the laminated structure can be adhesive layers of non-reducing adhesive force.

[0252] The adhesive layer (radiation-cured adhesive layer after radiation irradiation) formed of a radiation-curable adhesive is cured by radiation irradiation in advance, and even if the adhesive force is reduced by radiation irradiation, it still shows the adhesiveness brought by the contained polymer component, and can exert the minimum required adhesive force on the transfer sheet of the second embodiment. In the case of using a radiation-cured adhesive layer after radiation irradiation, in the surface extension direction of the second adhesive layer, the entire second adhesive layer can be a radiation-cured adhesive layer after radiation irradiation, a part of the second adhesive layer can be a radiation-cured adhesive layer after radiation irradiation and the other part is a radiation-cured adhesive layer not irradiated. It should be noted that in this specification, "radiation-cured adhesive layer" refers to an adhesive layer formed of a radiation-curable adhesive, including both a radiation-curable adhesive layer not irradiated with radiation curability and a radiation-cured adhesive layer after the adhesive layer is cured by radiation irradiation.

[0253] As the adhesive forming the pressure-sensitive adhesive layer, a known or commonly used pressure-sensitive adhesive can be used, and an acrylic adhesive having an acrylic polymer as a base polymer can be preferably used. In the case where the second adhesive layer contains an acrylic polymer as the pressure-sensitive adhesive, the acrylic polymer is preferably a polymer containing a structural unit derived from (meth)acrylate as the largest structural unit in terms of mass ratio. As the acrylic polymer, for example, the acrylic polymer described as the acrylic polymer that can be contained in the addition-type radiation-curable adhesive can be used.

[0254] [Base material]

[0255] The substrate in the transfer sheet of the second embodiment is a member that functions as a support. Examples of the substrate include plastic substrates (particularly plastic films). The substrate may be a single layer or a laminate of substrates of the same or different types.

[0256] Examples of the resin constituting the plastic substrate include low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, ultra-low-density polyethylene, random copolymer polypropylene, block copolymer polypropylene, homopolymer polypropylene, polybutene, polymethylpentene, ethylene-vinyl acetate copolymer (EVA), ionomer, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylate (random, alternating) copolymer, ethylene-butene copolymer, ethylene-hexene copolymer and other polyolefin resins; polyurethane; polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate, and polybutylene terephthalate (PBT); polycarbonate; polyimide; polyetheretherketone; polyetherimide; polyamides such as aromatic polyamide and wholly aromatic polyamide; polyphenylene sulfide; fluorine-containing resin; polyvinyl chloride; polyvinylidene chloride; cellulose resin; polysiloxane resin; cellulose triacetate (TAC), etc. When the electronic components received by the transfer sheet of the second embodiment are transferred to the mounting substrate for installation by heat compression bonding (for example, 150°C), the substrate preferably contains a heat-resistant resin such as polyimide (PI), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyamide (PA), polyether ether ketone (PEEK) as the main component, and more preferably contains polyimide as the main component, from the viewpoint of showing good heat resistance that is not easily caused by expansion and contraction due to heat and being able to be installed with high precision.

[0257] In addition, when the transfer sheet of the second embodiment receives electronic components, or when processing using active energy line irradiation such as laser irradiation is performed after receiving, from the viewpoint of preventing discoloration of the transfer sheet, polyimide (PI), polyethylene terephthalate (PET), triacetyl cellulose (TAC), etc. that show ultraviolet absorption are also preferred.

[0258] The main component of the base material refers to the component that occupies the largest mass ratio among the constituent components. The above-mentioned resins may be used alone or in combination of two or more.

[0259] When the substrate is a plastic film, the plastic film may be non-oriented or oriented in at least one direction (uniaxial direction, biaxial direction, etc.), but non-oriented is preferred because it is less likely to show heat shrinkage.

[0260] In order to improve the adhesion and retention of the adhesive layer, the first adhesive layer and / or the second adhesive layer side surface of the substrate can be subjected to physical treatments such as corona discharge treatment, plasma treatment, sandblasting, ozone exposure treatment, flame exposure treatment, high voltage electric shock exposure treatment, ionizing radiation treatment, etc.; chemical treatments such as chromic acid treatment; coating agent (primer); surface treatments such as easy adhesion treatment based on polysiloxane primer treatment. In addition, in order to impart antistatic ability, in addition to providing a conductive vapor deposition layer containing metals, alloys, their oxides, etc. on the surface of the substrate, a conductive polymer such as PEDOT-PSS can also be applied. The surface treatment for improving adhesion is preferably implemented on the entire surface of the adhesive layer side in the substrate.

[0261] From the viewpoint of ensuring the strength of the substrate for functioning as a support in the transfer sheet of the second embodiment, the thickness of the substrate is preferably 5 μm or more, more preferably 10 μm or more, further preferably 15 μm or more, and particularly preferably 20 μm or more. In addition, from the viewpoint of achieving appropriate flexibility in the transfer sheet of the second embodiment, the thickness of the substrate is preferably 200 μm or less, more preferably 180 μm or less, and further preferably 150 μm or less.

[0262] In the transfer sheet of the second embodiment, the haze of the substrate (according to JIS K7136) is not particularly limited, and is preferably 10% or less, and more preferably 5.0% or less. When the haze is 10% or less, excellent transparency can be obtained, for example, the visual recognition of the alignment mark formed by applying an external stimulus to the transfer sheet of the second embodiment is improved, which is preferred. It should be noted that the above haze can be measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").

[0263] In the transfer sheet of the second embodiment, the total light transmittance of the substrate in the visible light wavelength region (according to JIS K7361-1) is not particularly limited, preferably 85% or more, more preferably 88% or more. When the total light transmittance is 85% or more, excellent transparency can be obtained, for example, the visual recognition of the alignment mark formed by applying an external stimulus to the transfer sheet of the second embodiment is improved, which is preferred. It should be noted that the above-mentioned total light transmittance can be measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").

[0264] In the transfer sheet of the second embodiment, the color-changing component of the present invention may be contained in the substrate. That is, the substrate may contain a compound that changes color by reaction with an acid, an acid generator, and an alkali generator as required, and changes color by external stimulation, thereby forming an alignment mark. Alternatively, the substrate may also contain a compound that loses color by reaction with an alkali, an alkali generator, or a photochromic compound, and changes color by external stimulation, thereby forming an alignment mark.

[0265] The compound that changes color by reaction with an acid is preferably 0.01 to 30 parts by weight, more preferably 0.1 to 30 parts by weight, further preferably 0.1 to 20 parts by weight, and further preferably 1 to 10 parts by weight relative to 100 parts by weight of the substrate. When the content of the compound is within the above range, the alignment mark can be effectively formed by the color change caused by the compound that changes color by reaction with an acid.

[0266] The acid generator is preferably 0.001 to 30 parts by weight, more preferably 0.01 to 25 parts by weight, further preferably 0.1 to 30 parts by weight, and further preferably 0.1 to 20 parts by weight relative to 100 parts by weight of the substrate. When the content of the acid generator is within the above range, acid can be efficiently generated by irradiation with active energy rays or heating, and alignment marks can be effectively formed by discoloration caused by a compound that changes color by reaction with an acid.

[0267] The amount of the base generator is preferably 0.001 to 30 parts by weight, more preferably 0.01 to 25 parts by weight, and even more preferably 0.1 to 20 parts by weight relative to 100 parts by weight of the substrate. When the content of the base generator is within the above range, a base can be efficiently generated by irradiation with active energy rays or heating, and the alignment mark can be decolorized.

[0268] The content of the compound that loses color by reaction with a base and the photochromic compound in the substrate is the same as that of the compound that changes color by reaction with an acid.

[0269] [Release liner]

[0270] The adhesive layer surface (adhesive surface of the first adhesive layer and / or the second adhesive layer) of the transfer sheet of the second embodiment may be protected by a release liner before use. The release liner is used as a protective material for the adhesive layer and is removed when the adhesive sheet is attached to an adherend. Figure 2 The schematic cross-sectional view of one embodiment (second embodiment) of the transfer sheet of the present invention is shown in FIG. 1, the transfer sheet, 10, the substrate, 11, the first adhesive layer, 12, the second adhesive layer, and 110 and 120, release liners. In addition, the release liner may not necessarily be provided.

[0271] As the above-mentioned release liner, conventional release paper or the like can be utilized. Specifically, for example, in addition to a substrate having a release treatment layer based on a release treatment agent on at least one surface, a low-adhesive substrate comprising a fluorine-containing polymer (for example, polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc.), a low-adhesive substrate comprising a non-polar polymer (for example, olefin resins such as polyethylene and polypropylene, etc.), etc. can also be used.

[0272] As the release liner, for example, a release liner having a release treatment layer formed on at least one side of the release liner substrate can be preferably used. As such a release liner substrate, in addition to plastic substrate films (synthetic resin films) such as polyester films (polyethylene terephthalate films, etc.), olefin resin films (polyethylene films, polypropylene films, etc.), polyvinyl chloride films, polyimide films, polyamide films (nylon films), and rayon films, and papers (high-quality paper, Japanese paper, kraft paper, glass paper, synthetic paper, lacquered paper, etc.), substrates (complexes of 2 to 3 layers) obtained by multi-layering these by lamination, coextrusion, etc. can also be cited.

[0273] The release agent constituting the release layer is not particularly limited, and examples thereof include silicone release agents, fluorine-containing release agents, and long-chain alkyl release agents. The release agents may be used alone or in combination of two or more.

[0274] In addition, since the first pressure-sensitive adhesive layer is composed of a low-adhesive pressure-sensitive adhesive layer, a substrate that has not been treated with a release treatment agent may be used as a release liner.

[0275] In order to prevent adverse effects on electronic components, the release liner may have an antistatic layer formed on at least one side of the release liner substrate. The antistatic layer may be formed on one side (release treated side or untreated side) of the release liner, or may be formed on both sides (release treated side and untreated side) of the release liner.

[0276] Examples of the antistatic agent contained in the antistatic resin forming the antistatic layer include quaternary ammonium salts, pyridine Cationic antistatic agents having cationic functional groups such as sulfonates, sulfates, phosphonates, and phosphates, anionic antistatic agents having anionic functional groups such as sulfonates, sulfates, phosphonates, and phosphates, amphoteric antistatic agents such as alkyl betaines and their derivatives, imidazolines and their derivatives, alanine and their derivatives, nonionic antistatic agents such as amino alcohols and their derivatives, glycerol and their derivatives, polyethylene glycol and their derivatives, and ion conductive polymers obtained by polymerizing or copolymerizing monomers having the above-mentioned cationic, anionic, and zwitterionic ion conductive groups. These compounds can be used alone or in combination of two or more.

[0277] The thickness of the release liner is not particularly limited and can be appropriately selected from the range of 5 μm to 100 μm.

[0278] The method for producing the transfer sheet of the second embodiment varies depending on the composition of the pressure-sensitive adhesive composition, etc., and is not particularly limited. A known forming method can be used, and examples thereof include the following methods (1) to (4).

[0279] (1) A method of producing a PSA sheet by applying (coating) the PSA composition onto a substrate to form a composition layer, and curing the composition layer (for example, thermal curing or curing by irradiation with active energy rays such as ultraviolet rays) to form a PSA layer.

[0280] (2) A method of coating (applying) the above-mentioned adhesive composition on a release liner to form a composition layer, curing the composition layer (for example, thermal curing, curing by irradiation with active energy rays such as ultraviolet rays) to form an adhesive layer, and then transferring the adhesive layer to a substrate to produce an adhesive sheet.

[0281] (3) A method of manufacturing a pressure-sensitive adhesive sheet by applying (coating) the pressure-sensitive adhesive composition on a substrate and drying the composition to form a pressure-sensitive adhesive layer.

[0282] (4) A method of manufacturing a PSA sheet by coating (applying) the PSA composition onto a release liner and drying the coating to form a PSA layer, and then transferring the PSA layer onto a substrate.

[0283] As the curing method among the above (1) to (4), a thermal curing method is preferred from the viewpoint of excellent productivity and from the viewpoint of being able to form a uniform pressure-sensitive adhesive layer with a smooth surface.

[0284] As a method for applying (coating) the above-mentioned adhesive composition on a specified surface, a known coating method can be adopted without particular limitation, for example, extrusion coating methods such as roller coating, roller lick coating, gravure coating, reverse coating, roller brush, spray coating, dip roller coating, scraper bar coating, scraper knife coating, air knife coating, curtain coating, lip die coating, and die coating can be listed.

[0285] The thickness (total thickness) of the transfer sheet of the second embodiment is not particularly limited, and is preferably 10 μm or more, and more preferably 15 μm or more. When the thickness is above a certain value, the first adhesive layer can easily receive electronic components with high precision, which is preferred. In addition, the upper limit value of the thickness (total thickness) of the transfer sheet of the second embodiment is not particularly limited, and is preferably 500 μm or less, and more preferably 300 μm or less. When the thickness is below a certain value, it is easy to transfer electronic components to the mounting substrate with high precision, which is preferred. It should be noted that the thickness of the transfer sheet of the second embodiment does not include the thickness of the release liner.

[0286] The haze of the transfer sheet of the second embodiment (according to JIS K7136) is not particularly limited, preferably 10% or less, more preferably 5.0% or less. When the haze is 10% or less, excellent transparency can be obtained, for example, the visual recognition of the alignment mark formed by applying external stimulation to the transfer sheet of the second embodiment is improved, which is preferred. It should be noted that the above haze can be measured, for example, as follows: after the transfer sheet is left to stand for at least 24 hours under normal conditions (23° C., 50% RH), it is peeled off and attached to a slide glass (for example, a slide glass with a total light transmittance of 91.8% and a haze of 0.4%) with a release liner, and the obtained sample is used as a specimen and measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").

[0287] The total light transmittance (according to JIS K7361-1) in the visible light wavelength region of the transfer sheet of the second embodiment is not particularly limited, preferably 85% or more, more preferably 88% or more. When the total light transmittance is 85% or more, excellent transparency can be obtained, for example, the visual recognition of the alignment mark formed by applying external stimulation to the transfer sheet of the second embodiment is improved, which is preferred. It should be noted that the above-mentioned total light transmittance can be measured, for example, as follows: after the transfer sheet is left to stand for at least 24 hours under normal conditions (23° C., 50% RH), it is peeled off and attached to a slide glass (for example, a slide glass with a total light transmittance of 91.8% and a haze of 0.4%) with a release liner, and the obtained sample is used as a specimen and measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").

[0288] The transfer sheet of the present invention is suitable for receiving (transferring) electronic components. The method for transferring electronic components using the transfer sheet of the present invention preferably includes the following steps.

[0289] Applying an external stimulus to the transfer sheet of the present invention to form an alignment mark (first step);

[0290] The transfer sheet of the present invention receives the diced electronic components using the alignment marks as indices (second step).

[0291] Figure 3 This is a schematic cross-sectional view showing one embodiment of the first step in the method for transferring an electronic component using the transfer sheet of the second embodiment.

[0292] exist Figure 3 In (a), the transfer sheet 1 has a laminated structure in which a first adhesive layer 11, a substrate 10, and a second adhesive layer 12 are laminated in sequence. In the present embodiment, the second adhesive layer 12 contains the color-changing component of the present invention, and the first adhesive layer 11 does not contain the color-changing component of the present invention. In the present embodiment, the color-changing component contained in the second adhesive layer 12 includes a compound that changes color by reacting with an acid and a photoacid generator. The adhesive surface of the second adhesive layer 12 is attached to the carrier substrate 21. The carrier substrate can use a plastic substrate or a glass substrate similar to the aforementioned substrate, preferably a glass substrate with high transparency.

[0293] A photomask 22 is disposed on the surface of the carrier substrate 21 that is not bonded to the second adhesive layer 12. The openings of the photomask 22 correspond to positions where electronic components 31 described later are to be disposed on the second adhesive layer 11.

[0294] exist Figure 3 In (a), the active energy line U is irradiated to the photomask 22 side. The active energy line U passes through the opening of the photomask 22 and the highly transparent carrier substrate 21, reaches the second adhesive layer 12, the photoacid generator decomposes to generate acid, and the compound that changes color by reaction with the acid changes color (colors), forming an alignment mark 23 at a position corresponding to the opening of the photomask 22.

[0295] The active energy rays include ultraviolet rays, visible rays, infrared rays, α rays, β rays, γ rays, electron rays, neutron rays, X-rays, etc. Electron rays, ultraviolet rays, lasers are preferred, and ultraviolet rays are more preferred. The alignment mark 23 may be formed by irradiating a laser beam to a position corresponding to the opening of the photomask 22 without using the photomask 22.

[0296] Figure 4 It is a schematic cross-sectional view showing one embodiment of the second step in the method for transferring an electronic component using the transfer sheet of the second embodiment.

[0297] exist Figure 4 In (a), on the adhesive surface of the first adhesive layer 11 of the transfer sheet 1, a plurality of electronic components 31 separated by dicing are attached to the dicing tape 30 and arranged at intervals facing the adhesive surface of the first adhesive layer 11.

[0298] There is no particular limitation on the electronic component, and the electronic component can be suitably used for fine and thin semiconductor chips and LED chips. The electronic component can be a thin and fine electronic component, for example, the major diameter can be 500 μm or less, or 100 μm or less; the minor diameter can be 400 μm or less, or 50 μm or less. There is no particular limitation on the lower limit of the major diameter and the minor diameter, as long as it is 5 μm or more.

[0299] The thickness of the electronic component is not particularly limited, and may be 100 μm or less or 50 μm or less. The lower limit of the thickness of the electronic component is not particularly limited, and may be 5 μm or more.

[0300] exist Figure 4 In (b), the pin member 32 is used to push the electronic component 31 from the surface of the dicing tape 30 to which the electronic component 31 is not attached, so that the electronic component 31 is close to the adhesive surface of the first adhesive layer 11, so that the adhesive surface of the first adhesive layer 11 receives it. The position where the first adhesive layer 11 receives the electronic component 31 is aligned with the corresponding position using the alignment mark 23 as an indicator.

[0301] The receiving of the electronic component 31 can be performed by making the electronic component 31 contact with the first adhesive layer 11, or it can be performed in a non-contact manner. In the case of receiving in a non-contact manner, the electronic component 31 is pushed until the electronic component 31 is peeled off from the dicing tape 30, so that the electronic component 31 falls to the adhesive surface. In the case of receiving in a contact manner, since the adhesive surface of the first adhesive layer 11 has low adhesiveness, the stress when receiving the electronic component 31 is weak, so damage to the electronic component 31 can be suppressed. In the case of receiving in a non-contact manner, the adhesive surface of the first adhesive layer 11 has low adhesiveness, so the dropped electronic component 31 can be captured with good position accuracy.

[0302] In addition, the electronic component 31 may be peeled off from the dicing tape 30 by irradiating with radiation such as ultraviolet rays or laser beams instead of the pin member 32. When the electronic component 31 is peeled off from the dicing tape 30 by irradiating with radiation, the first adhesive layer 11 preferably contains an ultraviolet absorber. Since the first adhesive layer 11 contains an ultraviolet absorber, the radiation is absorbed by the first adhesive layer 11, and thus discoloration of the second adhesive layer 12 can be suppressed.

[0303] The electronic components 31 may be received by the first adhesive layer 11 individually or in a plurality at a time. Figure 4 (c) is a schematic cross-sectional view showing a state in which all the electronic components 31 of the dicing tape 20 are received on the adhesive surface of the first adhesive layer 11 of the transfer sheet 1 .

[0304] The electronic component 31 transferred onto the first adhesive layer 11 of the transfer sheet 1 is mounted on the mounting substrate. Figure 5 The cross-sectional view schematically shows a method of mounting electronic components transferred to the transfer sheet. In the present embodiment, the electronic components 31 are formed at positions accurately mounted on the respective circuits formed on the circuit surface 41 of the mounting substrate 40 using the alignment marks 23 as indices.

[0305] like Figure 5 As shown in (a), the electronic components 31 are arranged on the adhesive surface of the first adhesive layer 11 of the transfer sheet 1 at intervals and facing the circuit surface 41 (circuit pattern is not shown) of the mounting substrate 40. Figure 5 As shown in (b), the circuit surface 41 of the mounting substrate 40 is brought close to the electronic components 31 arranged on the adhesive surface of the first adhesive layer 11 of the transfer sheet 1, so that the electronic components 31 are in contact with the circuit surface 41 of the mounting substrate 40.

[0306] The transfer of the electronic component 31 to the circuit surface 41 of the mounting substrate 40 can also be performed by thermal compression bonding (e.g., 150° C., 1 minute). The base material 10, the first adhesive layer 11, and / or the second adhesive layer 12 constituting the transfer sheet 1 have excellent heat resistance, so that the adhesive force is not easily changed by expansion or contraction by thermal compression bonding, so that the electronic component 31 can be transferred to the circuit surface 41 of the mounting substrate 40 with good accuracy.

[0307] Then, if Figure 5 As shown in (c), by spacing the transfer sheet 1 and the mounting substrate 40, the electronic component 31 is peeled off from the first adhesive layer 11 and transferred to the circuit surface 41 of the mounting substrate 40. The first adhesive layer 11 is composed of a low-adhesive adhesive layer, so the electronic component 31 is easy to peel off, and the electronic component 31 is not damaged, and can be effectively mounted on the mounting substrate 40.

[0308] After the electronic component 31 is mounted on the mounting substrate 40 Figure 5 The transfer sheet 1 of (c) can also be peeled off from the carrier substrate 21 (not shown). Since the second adhesive layer 12 is composed of a peelable adhesive layer, it can be peeled off without adhesive residue and has excellent reworkability, so the carrier substrate 21 can be easily reused.

[0309] Example

[0310] The present invention is described in more detail with reference to the following examples, but the present invention is not limited to these examples.

[0311] [Production Example 1]: Production of acrylic copolymer (1)

[0312] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a cooler were placed 95 parts by weight of butyl acrylate (manufactured by Nippon Shokubai Co., Ltd.), 5 parts by weight of acrylic acid (manufactured by Toagosei Co., Ltd.), 0.2 parts by weight of 2,2'-azobisisobutyronitrile (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 156 parts by weight of ethyl acetate. Nitrogen was introduced while slowly stirring, and a polymerization reaction was carried out for 10 hours while maintaining the liquid temperature in the flask at approximately 63°C, thereby preparing a solution of an acrylic copolymer (1) having a weight average molecular weight of 700,000 (solid content: 40% by weight).

[0313] [Production Example 2]: Production of acrylic copolymer (2)

[0314] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a cooler were placed 100 parts by weight of 2-ethylhexyl acrylate (2EHA) (manufactured by Nippon Shokubai Co., Ltd.), 4 parts by weight of 2-hydroxyethyl acrylate (HEA) (manufactured by Toagosei Co., Ltd.), 0.02 parts by weight of 2,2'-azobisisobutyronitrile (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 180 parts by weight of ethyl acetate. Nitrogen was introduced while slowly stirring, and a polymerization reaction was carried out for 6 hours while maintaining the liquid temperature in the flask at approximately 65°C, thereby preparing a solution of an acrylic copolymer (2) having a weight average molecular weight of 560,000 (solid content: 35% by weight).

[0315] [Example 1]

[0316] (Production of transfer film)

[0317] 100 parts by weight of polysiloxane adhesive 1 (addition reaction type polysiloxane adhesive, trade name "X-40-3306", manufactured by Shin-Etsu Chemical Co., Ltd.), 1.4 parts by weight of platinum-containing catalyst 1 (trade name "CAT-PL-50T", manufactured by Shin-Etsu Chemical Co., Ltd.), and 5 parts by weight of polysiloxane release agent 1 (addition reaction type polysiloxane release agent with dimethylpolysiloxane as the main component, trade name "KS-776A", manufactured by Shin-Etsu Chemical Co., Ltd.), were added, diluted with toluene so that the total solid content became 25% by weight, and mixed using a disperser to prepare a polysiloxane adhesive composition (polysiloxane adhesive composition 1).

[0318] The polysiloxane adhesive composition 1 was applied to the polysiloxane primer-treated surface of a substrate film (1) (a polyester film having one surface treated with a polysiloxane primer, with a thickness of 25 μm, trade name "Diafoil MRF#25", manufactured by Mitsubishi Plastics Co., Ltd.) so that the thickness of the adhesive after drying would be 10 μm, and cured and dried under the conditions of a drying temperature of 120° C. and a drying time of 5 minutes. In this way, a film having a polysiloxane adhesive layer (1) on the polysiloxane primer-treated layer of the substrate film (1) was obtained.

[0319] It should be noted that a release liner (1) (polyethylene terephthalate film not subjected to release treatment, thickness 25 μm, trade name “Lumirror S10#25”, manufactured by Toray Industries, Ltd.) was attached to the adhesive surface of the polysiloxane-based adhesive film to protect the polysiloxane-based adhesive layer, thereby obtaining a laminate (1) having a laminate structure of [release liner (1) layer] / [polysiloxane-based adhesive (1) layer] / [substrate film (1) layer]].

[0320] Next, 6.0 parts by weight of TETRAD-C (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent, 2 parts by weight of a leuco dye (trade name "S-205", manufactured by Yamada Chemical Industry Co., Ltd.), and 7 parts by weight of a photoacid generator (trade name "CPI-100P", manufactured by San-Apro Co., Ltd.) were added to the solution of the acrylic copolymer (1) obtained in Production Example 1, based on 100 parts by weight of the solid content thereof. The mixture was diluted with toluene so that the total solid content became 25% by weight. The acrylic pressure-sensitive adhesive composition stirred by a disperser was applied by a fountain roll to the release-treated layer side of a release liner (2) (release-treated polyethylene terephthalate film, thickness 38 μm, trade name "MRF#38", manufactured by Mitsubishi Chemical Corporation) so that the thickness after drying became 25 μm. The mixture was cured and dried under the conditions of a drying temperature of 130° C. and a drying time of 30 seconds. Thus, an acrylic pressure-sensitive adhesive layer (1) is formed on the release liner (2).

[0321] Next, the substrate film (1) side (polysiloxane primer non-treated side) of the laminate (1) obtained above was bonded to the surface of the acrylic adhesive layer (1), thereby obtaining a transfer sheet having a laminate structure of [release liner (1) layer] / [polysiloxane adhesive (1) layer (first adhesive layer)] / [substrate film (1) layer] / [acrylic adhesive (1) layer (second adhesive layer)] / [release liner (2) layer].

[0322] [Example 2]

[0323] A transfer sheet having a laminated structure of [release liner (1) layer] / [polysiloxane adhesive (1) layer (first adhesive layer)] / [substrate film (1) layer] / [acrylic adhesive (2) layer (second adhesive layer)] / [release liner (2) layer] was obtained in the same manner as in Example 1 except that 7 parts by weight of a photoacid generator (trade name "CPI-110P", manufactured by SAN-Apro Co., Ltd.) was added instead of the photoacid generator (trade name "CPI-100P", manufactured by San-Apro Co., Ltd.).

[0324] [Example 3]

[0325] A transfer sheet having a laminated structure of [release liner (1) layer] / [polysiloxane adhesive (1) layer (first adhesive layer)] / [substrate film (1) layer] / [acrylic adhesive (3) layer (second adhesive layer)] / [release liner (2) layer] was obtained in the same manner as in Example 1 except that 7 parts by weight of a photoacid generator (trade name "CPI-310B", manufactured by San-Apro Co., Ltd.) was added instead of the photoacid generator (trade name "CPI-100P", manufactured by San-Apro Co., Ltd.).

[0326] [Example 4]

[0327] A transfer sheet having a laminated structure of [release liner (1) layer] / [polysiloxane adhesive (1) layer (first adhesive layer)] / [substrate film (2) layer] / [acrylic adhesive (4) layer (second adhesive layer)] / [release liner (2) layer] was obtained in the same manner as in Example 1, except that 7 parts by weight of a photoacid generator (trade name "SP-056", manufactured by ADEKA Corporation) was added instead of a photoacid generator (trade name "CPI-100P", manufactured by SAN-Apro Corporation) and substrate film (2) (polyimide film, thickness 25 μm, trade name "Kapton 100H", manufactured by DuPont Toray Co., Ltd.) was used instead of substrate film (1).

[0328] [Example 5]

[0329] A transfer sheet having a laminated structure of [release liner (1) layer] / [polysiloxane adhesive (1) layer (first adhesive layer)] / [substrate film (3) layer] / [acrylic adhesive (4) layer (second adhesive layer)] / [release liner (2) layer] was obtained in the same manner as in Example 4, except that a substrate film (3) (TAC film, thickness 80 μm, trade name "FUJITAC TD80UL", manufactured by Fujifilm Corporation) was used instead of the substrate film (2).

[0330] [Example 6]

[0331] 4.0 parts by weight of CORONATE HX (manufactured by Tosoh Corporation) as a crosslinking agent and 0.02 parts by weight of EMBILIZER 300 as a crosslinking catalyst were added to 100 parts by weight of the solid content of the acrylic copolymer (2) obtained in Preparation Example 2. OL-1 (manufactured by Tokyo Fine Chemical Co., Ltd.), 2 parts by weight of a leuco pigment (trade name "S-205", manufactured by Yamada Chemical Industry Co., Ltd.), and 7 parts by weight of a photoacid generator (trade name "SP-056", manufactured by Adeka Corporation), diluted with ethyl acetate so that the total solid content becomes 25% by weight, stirred with a disperser, and the resulting acrylic adhesive composition was applied to a release liner (2). The same operation as in Example 1 was carried out to obtain a transfer sheet having a laminated structure of [release liner (1) layer] / [polysiloxane adhesive (1) layer (first adhesive layer)] / [base film (1) layer] / [acrylic adhesive (5) layer (second adhesive layer)] / [release liner (2) layer].

[0332] [Example 7]

[0333] To a solution of CYABINE SH-109 (manufactured by Toyo Chemical Co., Ltd.) as a prepolymer type urethane adhesive composition (1), 3.0 parts by weight of CORONATE as a crosslinking agent was added based on 100 parts by weight of the solid content. HX (manufactured by Tosoh Corporation), 2 parts by weight of a leuco dye (trade name "S-205", manufactured by Yamada Chemical Industry Co., Ltd.), and 7 parts by weight of a photoacid generator (trade name "SP-056", manufactured by Adeka Corporation), diluted with ethyl acetate so that the total solid content becomes 25% by weight, stirred with a disperser, and the obtained urethane adhesive composition was applied to a release liner (2). The same operation as in Example 1 was carried out to obtain a transfer sheet having a laminated structure of [release liner (1) layer] / [polysiloxane adhesive (1) layer (first adhesive layer)] / [base film (1) layer] / [urethane adhesive (1) layer (second adhesive layer)] / [release liner (2) layer].

[0334] [Example 8]

[0335] 100 parts by weight of polysiloxane adhesive 1 (addition reaction type polysiloxane adhesive, trade name "X-40-3306", manufactured by Shin-Etsu Chemical Co., Ltd.), 1.4 parts by weight of platinum-containing catalyst 1 (trade name "CAT-PL-50T", manufactured by Shin-Etsu Chemical Co., Ltd.), 5 parts by weight of polysiloxane release agent 1 (addition reaction type polysiloxane release agent with dimethylpolysiloxane as the main component, trade name "KS-776A", manufactured by Shin-Etsu Chemical Co., Ltd.), and 5 parts by weight of ultraviolet absorber (trade name "TINUVIN384-2", manufactured by BASF) were added, diluted with toluene so that the total solid content became 25% by weight, and mixed using a disperser to prepare a polysiloxane adhesive composition (polysiloxane adhesive composition 2).

[0336] On a substrate film (4) (COP film, thickness 55 μm, trade name "Zeonor Film", manufactured by ZEON Corporation of Japan), a polysiloxane adhesive composition 2 was applied so that the thickness of the adhesive after drying became 10 μm, and cured and dried under the conditions of a drying temperature of 120° C. and a drying time of 5 minutes. Thus, a film having a polysiloxane adhesive layer (2) on the substrate film (4) was obtained.

[0337] It should be noted that a release liner (1) (polyethylene terephthalate film not subjected to release treatment, thickness 25 μm, trade name “Lumirror S10#25”, manufactured by Toray Industries, Ltd.) was adhered to the adhesive surface of the polysiloxane adhesive film to protect the polysiloxane adhesive layer, thereby obtaining a laminate (2) having a laminate structure of [release liner (1) layer] / [polysiloxane adhesive (2) layer] / [substrate film (4) layer]].

[0338] Next, 4.0 parts by weight of CORONATE HX (manufactured by Tosoh Corporation) as a crosslinking agent, 2 parts by weight of a leuco dye (trade name "S-205", manufactured by Yamada Chemical Industry Co., Ltd.), and 7 parts by weight of a photoacid generator (trade name "SP-056", manufactured by Adeka Corporation) were added to the solution of the acrylic copolymer (2) obtained in Production Example 2, based on 100 parts by weight of the solid content, and the mixture was diluted with toluene so that the total solid content became 25% by weight. The acrylic pressure-sensitive adhesive composition stirred by a disperser was applied by a fountain roll to the release-treated layer side of a release liner (2) (release-treated polyethylene terephthalate film, thickness 38 μm, trade name "MRF#38", manufactured by Mitsubishi Chemical Corporation) so that the thickness after drying became 25 μm, and then cured and dried under the conditions of a drying temperature of 130° C. and a drying time of 30 seconds. Thus, an acrylic pressure-sensitive adhesive layer (6) is formed on the release liner (2).

[0339] Next, the substrate film (4) side of the laminate (2) obtained above is bonded to the surface of the acrylic adhesive layer (6), thereby obtaining a transfer sheet having a laminate structure of [release liner (1) layer] / [polysiloxane adhesive (2) layer (first adhesive layer)] / [substrate film (4) layer] / [acrylic adhesive (6) layer (second adhesive layer)] / [release liner (2) layer].

[0340] [Comparative Example 1]

[0341] To 100 parts by weight of the solid content of the acrylic copolymer (2) obtained in Production Example 2, 6.0 parts by weight of TETRAD-C (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent, 4.0 parts by weight of CORONATE HX (manufactured by Tosoh Corporation) and 2 parts by weight of a leuco dye (trade name "S-205", manufactured by Yamada Chemical Industry Co., Ltd.) were added, the mixture was diluted with ethyl acetate so that the total solid content became 25% by weight, and the obtained acrylic pressure-sensitive adhesive composition was applied to a release liner (2) while stirring using a disperser. The same operation as in Example 1 was carried out to obtain a transfer sheet having a laminated structure of [release liner (1) layer] / [polysiloxane pressure-sensitive adhesive (1) layer (first pressure-sensitive adhesive layer)] / [substrate film (1) layer] / [acrylic pressure-sensitive adhesive (7) layer (second pressure-sensitive adhesive layer)] / [release liner (2) layer].

[0342] [Comparative Example 2]

[0343] To 100 parts by weight of the solid content of the acrylic copolymer (2) obtained in Production Example 2, 6.0 parts by weight of TETRAD-C (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent, 4.0 parts by weight of CORONATE HX (manufactured by Tosoh Corporation) and 7 parts by weight of a photoacid generator (trade name "SP-056", manufactured by Adeka Corporation) were added, diluted with ethyl acetate so that the total solid content became 25% by weight, stirred with a disperser, and the obtained acrylic pressure-sensitive adhesive composition was applied to a release liner (2). The same operation as in Example 1 was carried out, thereby obtaining a transfer sheet having a laminated structure of [release liner (1) layer] / [polysiloxane pressure-sensitive adhesive (1) layer (first pressure-sensitive adhesive layer)] / [substrate film (1) layer] / [acrylic pressure-sensitive adhesive (8) layer (second pressure-sensitive adhesive layer)] / [release liner (2) layer]

[0344] <Evaluation>

[0345] The transfer sheets obtained in Examples and Comparative Examples were evaluated as follows.

[0346] (Total transmittance change)

[0347] After peeling off the release liners on both sides of the transfer sheet having a laminated structure of each example, the initial total light transmittance was measured using a haze meter ("HM-150" manufactured by Murakami Color Research Laboratory) so that the first adhesive layer side was arranged on the light source side.

[0348] Next, a UV irradiation device (UV LIGHT SOURCE UL750, manufactured by HOYA) was used through the release liner (2) at an irradiation intensity of 100 mW / cm 2 、Accumulated light quantity 1000mJ / cm 2 The second adhesive layer is discolored by light, and after peeling off the release liners on both sides, the total light transmittance after the color change is measured using a haze meter in the same manner as the initial total light transmittance, and the absolute value of the difference between the initial total light transmittance and the total light transmittance after the color change is taken as the change in total light transmittance.

[0349] (Alignment)

[0350] A photomask having alignment marks with a line width of 300 μm was placed on the release liner (2) of the transfer sheet of each example, and a UV irradiation device (UV LIGHT SOURCE UL750, manufactured by HOYA) was used through the photomask at an irradiation intensity of 100 mW / cm 2 、Accumulated light quantity 1000mJ / cm 2 Then, the release liner (2) was peeled off, and the second adhesive layer was attached to the alkali-free glass. The alignment mark was read through the glass by the following method and evaluated.

[0351] CCD camera: CA-H500C (manufactured by KEYENCE)

[0352] Analysis: ShapeTrax3 (manufactured by KEYENCE)

[0353] Judgment: When the correlation value is greater than 90, it is judged as 0, and when it is less than 90, it is judged as ×.

[0354] (Discoloration caused by external light irradiation from the sheet side)

[0355] After peeling off the release liner (2) of the transfer sheet of each example, the second adhesive layer was attached to the alkali-free glass, thereby preparing the evaluation sample. Then, the release liner (1) was peeled off, and the adhesive sheet of each embodiment and each comparative example was placed for 240 hours in a manner of irradiating the light of a fluorescent lamp from the first adhesive layer side, and visually confirmed whether there was discoloration. The case where no discoloration was confirmed was judged as 0, and the case where discoloration was confirmed was judged as ×. It should be noted that Comparative Examples 1 and 2 do not have alignment (discoloration), so of course no discoloration was confirmed.

[0356]

[0357] Modifications of the present invention will be described below.

[0358] [Note 1]

[0359] A transfer sheet for receiving an electronic component, wherein the transfer sheet contains a color-changing component capable of changing color by external stimulation.

[0360] [Note 2]

[0361] The transfer sheet according to Supplementary Note 1, wherein the electronic component is a semiconductor chip.

[0362] [Note 3]

[0363] The transfer sheet according to Supplementary Note 1 or 2, wherein the major diameter of the electronic component is 500 μm or less.

[0364] [Note 4]

[0365] The transfer sheet according to any one of Appendixes 1 to 3, wherein the transfer sheet has a pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer contains the color-changing component.

[0366] [Note 5]

[0367] The transfer sheet according to Supplementary Note 4, wherein the adhesive constituting the adhesive layer is an acrylic adhesive or a urethane adhesive.

[0368] [Note 6]

[0369] The transfer sheet according to Supplementary Note 4 or 5, wherein the transfer sheet has a laminated structure in which the adhesive layer, a substrate, and another adhesive layer different from the adhesive layer are laminated in this order.

[0370] Description of symbols

[0371] 1 transfer sheet

[0372] 10. Base material

[0373] 11 first adhesive layer

[0374] 12 Second adhesive layer

[0375] 110, 120 release liner

[0376] 21 Carrier substrate

[0377] 22 Photomask

[0378] U Active Energy Line

[0379] 23 Alignment mark (color change part)

[0380] 30 cutting belt

[0381] 31 Electronic components

[0382] 32-pin components

[0383] 40 Mounting substrate

[0384] 41 Circuit surface

Claims

1. A transfer sheet for receiving an electronic component, wherein: The transfer sheet contains a color-changing component that changes color when stimulated by an external stimulus.

2. The transfer sheet according to claim 1, wherein The electronic component is a semiconductor chip.

3. The transfer sheet according to claim 1 or 2, wherein: The electronic component has a major diameter of 500 μm or less.

4. The transfer sheet according to any one of claims 1 to 3, wherein The transfer sheet has an adhesive layer, and the adhesive layer contains the color-changing component.

5. The transfer sheet according to claim 4, wherein The adhesive constituting the adhesive layer is an acrylic adhesive or a urethane adhesive.

6. The transfer sheet according to claim 4 or 5, wherein: The transfer sheet has a laminated structure in which the adhesive layer, a substrate, and another adhesive layer different from the adhesive layer are laminated in this order.

Citation Information

Patent Citations

  • Adhesive metal sheet for fixing semiconductor wafer

    JP1985196956A

  • Dicing die-bonding film

    JP2019009203A

  • Element transfer member, method for manufacturing element transfer member and method for manufacturing semiconductor device

    JP2021197400A

Cited By

  • Film material for laser transfer printing

    CN119217826A